Composite negative electrode active material, negative electrode and lithium battery employing same, and preparation method of composite negative electrode active material
By using a composite negative electrode active material containing a silicon composite structure, a first carbon-type coating and a second amorphous carbon in the negative electrode of the lithium battery, the problem of deterioration of the silicon negative electrode active material during the circulation process is solved, and the energy density and circulation characteristics of the lithium battery are improved.
Patent Information
- Application Number
- CN202380061505.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-23
- Filing Date
- 2023-08-22
- Publication Date
- 2025-04-04
AI Technical Summary
The existing silicon-based negative electrode active substances are prone to deterioration due to volume changes during the circulation of lithium batteries, resulting in poor energy density and circulation characteristics of lithium batteries.
A composite negative electrode active material is used, which includes a silicon-containing composite structure, a first carbon-based coating and a second amorphous carbon. The silicon-containing composite structure consists of porous silicon secondary particles and a first carbon sheet, and the second amorphous carbon is arranged in the silicon-containing composite structure and contains heterogeneous elements.
With this composite negative electrode active material, the discharge capacity of the lithium battery increases, and the cycle characteristics are improved, thereby avoiding deterioration of silicon and increasing internal resistance.
Smart Images

Figure CN119768931A_ABST
Abstract
Description
Technical Field
[0001] One or more embodiments relate to a composite negative electrode active material, a negative electrode and a lithium battery using the composite negative electrode active material, and a method for preparing the composite negative electrode active material. Background Art
[0002] As various devices become increasingly miniaturized and have higher performance, it has become important for lithium batteries to have higher energy density as well as miniaturization and weight reduction. That is, lithium batteries with high capacity are becoming more and more important.
[0003] In order to realize lithium batteries suitable for the above-mentioned applications, research on negative electrode active materials having high capacity is underway.
[0004] Compared with carbon-based negative electrode active materials, existing silicon-based negative electrode active materials are more easily degraded due to volume changes during cycling.
[0005] Under such circumstances, there is a need for a lithium battery that includes a silicon-based negative active material and also provides improved cycle characteristics. Summary of the invention
[0006] Technical issues
[0007] One or more embodiments include a novel composite negative active material capable of preventing lithium batteries from deteriorating.
[0008] One or more embodiments include a negative electrode including the composite negative electrode active material.
[0009] One or more embodiments include a lithium battery using the negative electrode.
[0010] Technical Solution
[0011] According to one or more embodiments, the composite negative electrode active material includes:
[0012] Silicon-containing composite structure;
[0013] a first carbon-based coating including a first amorphous carbon and disposed on the silicon-containing composite structure; and
[0014] a second amorphous carbon disposed in the silicon-containing composite structure,
[0015] The silicon-containing composite structure may include: porous silicon secondary particles; and a first carbon sheet disposed on the porous silicon secondary particles.
[0016] The porous silicon secondary particles may each comprise an aggregate comprising a plurality of silicon composite primary particles,
[0017] The silicon composite primary particles may include: silicon; silicon dioxide (SiO x, where 0 < x < 2), disposed on silicon; and a second carbon sheet, disposed on silicon suboxide,
[0018] The second amorphous carbon may be disposed in the pores of the porous silicon secondary particles, and
[0019] The second amorphous carbon may include a hetero element belonging to at least one of Group 15 and Group 17 selected from the Periodic Table of the Elements.
[0020] According to one or more embodiments,
[0021] The negative electrode includes a composite negative electrode active material.
[0022] According to one or more embodiments, a lithium battery includes:
[0023] A positive electrode; the above-mentioned negative electrode; and
[0024] An electrolyte, between the positive electrode and the negative electrode.
[0025] According to one or more embodiments,
[0026] A method for preparing a composite negative electrode active material includes the following steps: providing porous silicon secondary particles;
[0027] Preparing a silicon-containing composite structure by supplying a carbon source gas to the porous silicon secondary particles and performing heat treatment on the porous silicon secondary particles;
[0028] Preparing a first composition, the first composition including a silicon-containing composite structure, an amorphous carbon precursor containing a hetero element selected from Group 15 or Group 17 of the Periodic Table of the Elements, and an additive; and
[0029] Preparing a composite negative electrode active material by performing heat treatment on the first composition at a temperature of 350 °C or lower,
[0030] wherein the composite negative electrode active material may include:
[0031] A silicon-containing composite structure;
[0032] A first carbonaceous coating, including first amorphous carbon, and disposed on the silicon-containing composite structure; and
[0033] A second amorphous carbon, disposed within the silicon-containing composite structure,
[0034] wherein the silicon-containing composite structure may include: porous silicon secondary particles; and a first carbon sheet, disposed on the porous silicon secondary particles,
[0035] The porous silicon secondary particles may each include an aggregate containing a plurality of silicon composite primary particles,
[0036] wherein the silicon composite primary particles may include silicon, silicon suboxide (SiO disposed on siliconx , where \(0 \lt x \lt 2\)), and a second carbon sheet disposed on the silicon monoxide,
[0037] The second amorphous carbon may be disposed in the pores of the porous silicon secondary particles, and
[0038] The second amorphous carbon may include a hetero element belonging to at least one of Group 15 and Group 17 selected from the periodic table of elements.
[0039] Beneficial effects
[0040] According to one aspect, since the composite negative electrode active material includes the second amorphous carbon doped with a hetero element, the lithium battery can have an increased discharge capacity and improved cycle characteristics. Description of the drawings
[0041] Figure 1a is a schematic cross-sectional view of a composite negative electrode active material according to an embodiment.
[0042] Figure 1b is a schematic cross-sectional view of a composite negative electrode active material according to an embodiment.
[0043] Figure 1c is a schematic cross-sectional view of a composite negative electrode active material according to an embodiment.
[0044] Figure 1d is a schematic cross-sectional view of a composite negative electrode active material according to an embodiment.
[0045] Figure 2a is a scanning electron microscope image of a composite negative electrode active material prepared in Comparative Example 2.
[0046] Figure 2b is a scanning electron microscope image of a composite negative electrode active material prepared in Comparative Example 2.
[0047] Figure 2c is a scanning electron microscope image of a composite negative electrode active material prepared in Example 1.
[0048] Figure 2d is a scanning electron microscope image of a composite negative electrode active material prepared in Example 1.
[0049] Figure 2e is a scanning electron microscope image of a composite negative electrode active material prepared in Example 5.
[0050] Figure 2f is a scanning electron microscope image of a composite negative electrode active material prepared in Example 5.
[0051] Figure 3a is a HAADF-STEM image of a cross-section of a composite negative electrode active material prepared in Example 1.
[0052] Figure 3b This is a TEM-EDS mapping image of the silicon element in the cross section of the composite negative electrode active material prepared in Example 1.
[0053] Figure 3c This is a TEM-EDS mapping image of the carbon element in the cross section of the composite negative electrode active material prepared in Example 1.
[0054] Figure 3d This is a TEM-EDS mapping image of the fluorine element in the cross section of the composite negative electrode active material prepared in Example 1.
[0055] Figure 3e This is an image of a region selected from the HAADF-STEM image of the cross section of the composite negative electrode active material prepared in Example 1 and used for EDS analysis.
[0056] Figure 3f This is an image of a region selected from a TEM-EDS mapping image of fluorine element in a cross section of the composite negative electrode active material prepared in Example 1 and used for EDS analysis.
[0057] Figure 4a is a Nyquist diagram showing impedance measurement results of the lithium batteries of Example 11 and Comparative Example 13 before cycling.
[0058] Figure 4b is a Nyquist plot showing impedance measurement results of the lithium batteries of Example 11 and Comparative Example 13 after cycling.
[0059] Figure 5 is a schematic diagram of a lithium battery according to an embodiment.
[0060] Figure 6 is a schematic diagram of a lithium battery according to an embodiment.
[0061] Figure 7 is a schematic diagram of a lithium battery according to an embodiment.
[0062] <Explanation of Reference Symbols Designating Main Elements of the Drawings>
[0063] 1: Lithium battery; 2: Negative electrode
[0064] 3: positive electrode; 4: diaphragm
[0065] 5: Battery housing; 6: Cover assembly
[0066] 7: Battery structure; 8: Electrode terminal block
[0067] 10: Composite negative electrode active material; 20: Porous silicon secondary particles
[0068] 30: Silicon-containing composite structure; 100: Composite negative electrode active material
[0069] 110: Silicon; 120: Carbon sheet
[0070] 120a: first carbon sheet; 120b: second carbon sheet
[0071] 130: Silicon oxide; 140: Amorphous carbon
[0072] 140a: first amorphous carbon; 140b: second amorphous carbon
[0073] 150: First carbon type coating; 160: Second carbon type coating DETAILED DESCRIPTION
[0074] Now will refer to embodiment in detail, the example of embodiment is shown in the accompanying drawings, wherein the same reference numerals refer to the same element from time to time. In this regard, the embodiment provided may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the embodiment is described below only by reference to the accompanying drawings to explain the aspects of this specification. As used herein, the term "and / or" includes any combination and all combinations of one or more of the related listed items. Statements such as "at least one (kind / person) of ... " modify the entire column of elements when following a column of elements, without modifying the individual elements of the column.
[0075] The inventive concept, which will be described more fully below, may have various modifications and various embodiments, and specific embodiments will be shown and described in more detail in the accompanying drawings. However, the inventive concept should not be interpreted as being limited to the specific embodiments set forth herein. On the contrary, these embodiments will be understood to encompass all modifications, equivalents or substitutes included within the scope of the inventive concept.
[0076] The terms used hereinafter are only used for the purpose of describing specific embodiments and are not intended to limit the inventive concept. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. As used herein, when the terms "include", "comprise" and / or its variations are used in this specification, it is indicated that there are stated features, regions, integers, steps, operations, elements, components, ingredients, materials or combinations thereof, but it is not excluded that there are or add one or more other features, regions, integers, steps, operations, elements, components, ingredients, materials or combinations thereof. As used herein, " / " can be interpreted as "and" or "or" according to the context.
[0077] In the drawings, for clarity of description, the thickness of layers and regions may be exaggerated. Throughout the specification, like reference numerals denote like elements. Throughout the specification, when a component such as a layer, film, region, or plate is described as being "on" or "above" another component, the component may be directly on top of the other component, or there may be another component therebetween. It will be understood that although terms such as "first", "second", etc. may be used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another.
[0078] In the present application, if the particles are spherical, the term "particle size" of the particles refers to the average particle size, and for non-spherical particles, the term refers to the average major axis length of the particles. The particle size of the particles can be measured using a particle size analyzer (PSA). The term "particle size" of the particles can be, for example, the average diameter of the particles. Unless otherwise explicitly stated, the average particle size refers to the median particle size (D50). The median particle size (D50) refers to the particle size on the particle size distribution curve where the particles accumulate from the smallest particle size to the largest particle size and corresponds to the cumulative volume of 50 vol% counted from the smallest particle size. The cumulative value can be, for example, the cumulative volume. The median particle size (D50) can be measured by, for example, laser diffraction method.
[0079] As used herein, the particle size (D10) refers to the particle size on the cumulative particle size distribution curve that corresponds to the cumulative volume of 10 vol% counted from the smallest particle size.
[0080] As used herein, the particle size (D90) refers to the particle size on the cumulative particle size distribution curve that corresponds to the cumulative volume of 90 vol% counted from the smallest particle size.
[0081] As used herein, "silicon monoxide" may have, for example, a uniform composition represented by SiO x (0 < x < 2). Optionally, "silicon monoxide" may include one or more selected from Si and SiO2, and thus has a composition generally represented by SiO x (0 < x < 2). In addition, "silicon monoxide" may also include, for example, silicon monoxide-like materials. Silicon monoxide-like materials may be materials having properties similar to those of silicon monoxide and include, for example, one or more selected from Si and SiO2, and thus have a composition generally represented by SiO x (0 < x < 2).
[0082] Hereinafter, the composite negative electrode active material according to an exemplary embodiment, and the negative electrode and the lithium battery including the same will be described in more detail.
[0083] The composite negative electrode active material may include: a silicon-containing composite structure; a first carbonaceous coating including first amorphous carbon and disposed on the silicon-containing composite structure; and second amorphous carbon disposed within the silicon-containing composite structure, wherein the silicon-containing composite structure may include porous silicon secondary particles and a first carbon sheet disposed on the porous silicon secondary particles, wherein the porous silicon secondary particles may each include an aggregate of a plurality of silicon composite primary particles, and wherein the silicon composite primary particles may include silicon, silicon suboxide (SiO x , 0 < x < 2) disposed on the silicon, and a second carbon sheet disposed on the silicon suboxide, and wherein the second amorphous carbon may be disposed in the pores of the porous silicon secondary particles and the second amorphous carbon may include a hetero element belonging to at least one of Group 15 and Group 17 in the periodic table.
[0084] Referring Figure 1a to Figure 1d , the composite negative electrode active material 100 may include: a silicon-containing composite structure 30; a first carbonaceous coating 150 including first amorphous carbon 140a and disposed on the silicon-containing composite structure 30; and second amorphous carbon 140b disposed within the silicon-containing composite structure 30, wherein the silicon-containing composite structure 30 may include porous silicon secondary particles 20 and a first carbon sheet 120a disposed on the porous silicon secondary particles 20, wherein the porous silicon secondary particles 20 may each include an aggregate of a plurality of silicon composite primary particles 10, and wherein the silicon composite primary particles 10 may include silicon 110, silicon suboxide 130 (SiO x , 0 < x < 2) disposed on the silicon 110, and a second carbon sheet 120b disposed on the silicon suboxide 130, and wherein the second amorphous carbon 140b may be disposed in the pores of the porous silicon secondary particles 20 and the second amorphous carbon 140b may include a hetero element belonging to at least one of Group 15 and Group 17 in the periodic table. As Figure 1b and Figure 1d shown in, the carbon sheet 120 may include a first carbon sheet 120a and a second carbon sheet 120b. The composite negative electrode active material 100 may have a structure including, for example, a core and a shell disposed on the surface of the core and conformal with the surface of the core. The core may include the silicon-containing composite structure 30 and the second amorphous carbon 140b disposed within the silicon-containing composite structure 30. The shell may be disposed on the silicon-containing composite structure 30 and include the first carbonaceous coating 150. The first carbonaceous coating 150 may include first amorphous carbon 140a.
[0085] Hereinafter, the following description is provided for the purpose of providing a theoretical basis to support the excellent effects of the composite negative electrode active material according to the embodiments; however, it should be understood that the description is provided for further understanding of the inventive concept disclosed herein and should not be construed as limiting the inventive concept in any way.
[0086] The composite negative electrode active material may include a second amorphous carbon filling the interior of the silicon-containing composite structure, and since a heterogeneous element is included in the second amorphous carbon, the side reaction caused by the contact between the electrolyte and the silicon in the composite negative electrode active material during the cycle of the lithium battery can be effectively suppressed. For example, since a lithium compound derived from the heterogeneous element included in the second amorphous carbon is formed in the composite negative electrode active material, a solid electrolyte interface (SEI) with improved conductivity, mechanical properties and stability can be formed inside and / or on the surface of the composite negative electrode active material. The lithium compound generated in the composite negative electrode active material may be, for example, a lithium salt, lithium oxide, lithium nitride, lithium oxynitride, lithium phosphate, etc. Therefore, during the cycle of the lithium battery, the side reaction between silicon and the electrolyte can be more effectively suppressed. In addition, since an insulating SEI is formed inside and / or on the surface of the composite negative electrode active material during the cycle of the lithium battery, the increase in the internal resistance of the lithium battery can be suppressed.
[0087] In addition, including the first carbon sheet and the second carbon sheet in the composite negative electrode active material can effectively adapt to the volume change of silicon during the cycle of the lithium battery. Therefore, the rupture and isolation of silicon caused by the volume change of silicon during the cycle of the lithium battery can be prevented. Therefore, the capacity loss of the composite negative electrode active material can be effectively prevented. In addition, the separation between silicon and the carbonaceous material caused by the volume change of silicon during the cycle of the lithium battery can be prevented. Therefore, the increase in the internal resistance of the lithium battery can be effectively suppressed. As a result, the lithium battery including the composite negative electrode active material can have improved discharge capacity and cycle characteristics.
[0088] The heterogeneous element included in the second amorphous carbon 140b may be, for example, at least one selected from fluorine (F), nitrogen (N), and phosphorus (P). The heterogeneous element may be, for example, fluorine (F). The presence of the heterogeneous element in the composite negative active material 100 may be confirmed by thermogravimetric analysis, ion chromatography, and the like.
[0089] Based on the STEM-EDS analysis of the cross section of the composite negative active material 100, the content of the foreign element may be, for example, about 0.1 wt % to about 10 wt %, or about 0.1 wt % to about 5 wt % relative to the total element content included in the silicon-containing composite structure 30 in which the second amorphous carbon 140 b is disposed. Based on the energy dispersive X-ray spectrometer (EDS) spectrum of the silicon-containing composite structure 30 including the second amorphous carbon 140 b, the content of the foreign element may be, for example, about 0.1 wt % to about 10 wt %, about 0.1 wt % to about 5 wt %, or about 0.1 wt % to about 3.5 wt % relative to the total element content.
[0090] The porous silicon secondary particle 20 may be an aggregate of a plurality of silicon composite primary particles 10, and the silicon composite primary particles 10 may include: silicon 110; silicon 20 oxide 130 (SiOx For 0 < x < 2), it is disposed on silicon 110; and a second carbon sheet 120b is disposed on silicon suboxide 130. The second carbon sheet 120b disposed on silicon suboxide 130 can be arranged to cover at least one surface of silicon suboxide 130. The second carbon sheet 120b can be directly disposed on silicon suboxide 130. The second carbon sheet 120b can grow directly from the surface of silicon suboxide 130 and be directly disposed on the surface of silicon suboxide 130. For example, the second carbon sheet 120b can completely or partially cover the surface of silicon suboxide 130. With respect to the total surface area of silicon suboxide 130, the coverage rate of the second carbon sheet 120b can be, for example, about 10% to 100%, about 10% to about 99%, about 20% to about 95%, or about 40% to about 90%. Carbon in the second carbon sheet 120b can exist on the surface of silicon 110 and / or silicon suboxide 130 to effectively buffer the volume change of the silicon composite primary particles 10. For example, the second carbon sheet 120b can have a size of about 1 nm to about 200 nm, about 5 nm to about 150 nm, or about 10 nm to about 100 nm. Here, the size refers to the diameter or the length of the major axis.
[0091] The second amorphous carbon 140b can be disposed in the pores of the porous silicon secondary particles 20. The porous silicon secondary particles 20 can each include an aggregate of a plurality of silicon composite primary particles 10, and the second amorphous carbon 140b can be disposed between adjacent silicon composite primary particles 10. For example, the second amorphous carbon 140b can be disposed on the second carbon sheet 120b. The second amorphous carbon 140b can be disposed on the second carbon sheet 120b included in the silicon composite primary particles 10. Therefore, the second amorphous carbon 140b can be spaced apart from silicon 110 and / or silicon suboxide 130 by the second carbon sheet 120b. The second carbon sheet 120b can serve as a buffer layer between silicon 110 and the second amorphous carbon 140b. Therefore, the second carbon sheet 120b can be used to effectively accommodate the volume change of silicon 110 while maintaining the conductivity between silicon 110 and the second amorphous carbon 140b. In the second amorphous carbon 140b, a hetero element can be disposed adjacent to, for example, silicon 110. Refer to Figure 3d , a hetero element, such as fluorine (F), can be disposed adjacent to silicon 110. Since the hetero element is disposed adjacent to silicon 100, a solid electrolyte interface (SEI) with improved conductivity and mechanical properties can be formed in the region adjacent to silicon 110, thereby effectively preventing the deterioration of silicon 110.
[0092] The composite negative electrode active material 100 can include a first carbon-based coating 150 disposed on the silicon-containing composite structure 30, and the first carbon-based coating 150 can include a first amorphous carbon 140a.
[0093] The first amorphous carbon 140a may include a foreign element. The foreign element included in the first amorphous carbon 140a may be, for example, at least one selected from fluorine (F), nitrogen (N), and phosphorus (P). The foreign element may be, for example, fluorine (F).
[0094] Based on the STEM-EDS analysis of the cross section of the composite negative active material 100, the content of the foreign element may be, for example, about 0.1 wt % to about 10 wt %, or about 0.1 wt % to about 5 wt % relative to the total element content included in the silicon-containing composite structure 30 coated with the first carbon-based coating layer including the first amorphous carbon. Based on the EDS spectrum of the first carbon-based coating layer 150 including the first amorphous carbon 140a, the content of the foreign element may be, for example, about 0.1 wt % to about 10 wt %, or about 0.1 wt % to about 5 wt % relative to the total element content.
[0095] For example, the content of the heterogeneous elements included in the composite negative electrode active material 100 may be about 0.1 wt % to about 10 wt %, or about 0.1 wt % to about 5 wt % relative to the total weight of the composite negative electrode active material 100. Since the composite negative electrode active material 100 includes the heterogeneous elements within the above range, further improvement in the cycle characteristics of the lithium battery including the composite negative electrode active material 100 may be achieved. The content of the heterogeneous elements included in the composite negative electrode active material 100 may be confirmed by, for example, X-ray photoelectron spectroscopy (XPS), energy dispersive X-ray spectrometer (EDS), and the like.
[0096] The silicon-containing composite structure 30 may include, for example, a porous silicon secondary particle 20 and a first carbon sheet 120 a disposed on the porous silicon secondary particle 20 .
[0097] The first carbon sheet 120a disposed on the porous silicon secondary particle 20 may be disposed to cover at least one surface of the porous silicon secondary particle 20. The first carbon sheet 120a may be directly disposed on the porous silicon secondary particle 20. The first carbon sheet 120a may grow directly from the surface of the porous silicon secondary particle 20. The first carbon sheet 120a may grow directly from the surface of the porous silicon secondary particle 20 and be directly disposed on the surface of the porous silicon secondary particle 20. The first carbon sheet 120a may completely or partially cover the surface of the porous silicon secondary particle 20. The coverage of the first carbon sheet 120a may be, for example, about 5% to 100%, about 10% to about 99%, about 20% to about 95%, or about 40% to about 90% relative to the total surface area of the porous silicon secondary particle 20. The carbon in the first carbon sheet 120a may be present on the surface of the porous silicon secondary particle 20 to effectively buffer the volume change of the porous silicon secondary particle 20. For example, the porous silicon secondary particle 20 may have a size of about 1 μm to about 10 μm, about 2 μm to about 8 μm, or about 3 μm to about 7 μm. For example, the first carbon sheet 120a may have a size of about 1 nm to about 200 nm, about 5 nm to about 150 nm, or about 10 nm to about 100 nm. Here, the size refers to the diameter or the major axis length.
[0098] The silicon-containing composite structure 30 may include a porous silicon secondary particle 20, and a first amorphous carbon 140a may be disposed on the porous silicon secondary particle 20. The first amorphous carbon 140a may form a first carbon-based coating 150. For example, the first amorphous carbon 140a may be disposed on a first carbon sheet 120a. The first amorphous carbon 140a may be disposed on the first carbon sheet 120a included in the silicon-containing composite structure 30. Therefore, the first amorphous carbon 140a may be separated from the silicon 110 and / or silicon monoxide 130 included in the porous silicon secondary particle 20 by the first carbon sheet 120a. The first carbon sheet 120a may be used as a buffer layer between the silicon 110 and the first amorphous carbon 140a. Therefore, the first carbon sheet 120a may be used to effectively accommodate the volume change of the silicon 110 while maintaining the conductivity between the silicon 110 and the first amorphous carbon 140a.
[0099] The composite negative electrode active material 100 may have a porosity of, for example, 30% or less, 20% or less, 10% or less, 5% or less, 3% or less, or 1% or less. For example, the composite negative electrode active material may be nonporous. The porosity of the composite negative electrode active material may be, for example, 0% to about 30%, 0% to about 20%, 0% to about 10%, or 0% to about 5%. The porosity of the composite negative electrode active material may be, for example, about 0.01% to about 5%, or 0%. The pores may be substantially absent from a scanning electron microscope image of a cross section of the composite negative electrode active material. The porosity of the composite negative electrode active material may be calculated, for example, by the ratio of the area occupied by the pores to the area of the total cross section in a scanning electron microscope image of a cross section of the composite negative electrode active material. Alternatively, the porosity of the composite negative electrode active material may be measured by mercury porosimetry or nitrogen porosimetry.
[0100] The first carbon-based coating 150 disposed on the silicon-containing composite structure 30 may be non-porous. Substantially no pores may be observed from a scanning electron microscope image of a cross section of the first carbon-based coating 150.
[0101] The first carbon-based coating 150 may have a thickness of, for example, about 1 nm to about 5,000 nm, about 10 nm to about 2,000 nm, or about 5 nm to about 2,500 nm. Since the first carbon-based coating has a thickness within the above range, further improvement in the cycle characteristics of a lithium battery using a composite negative electrode active material may be achieved.
[0102] The silicon-containing composite structure 30 may include a first carbon sheet 120a and a second carbon sheet 120b. For example, the first carbon sheet 120a and the second carbon sheet 120b may be carbon sheets that are identical to each other. The first carbon sheet 120a and the second carbon sheet 120b may be any carbon-based material having a sheet shape. The first carbon sheet 120a and the second carbon sheet 120b may be, for example, each independently selected from graphene, graphite, carbon fiber, graphite carbon, graphene oxide, or a mixture thereof. The silicon-containing composite structure 30 may include, for example, a first graphene and a second graphene as the first carbon sheet 120a and the second carbon sheet 120b, respectively. The first graphene and the second graphene may each have a structure such as a nanosheet, a film (or a thin film) or a sheet. The term "nanosheet" refers to a graphene structure formed in an irregular form on silicon oxide or porous silicon secondary particles to a thickness of 1,000nm or less (e.g., about 1nm to about 1,000nm). The term "thin film" refers to a continuous uniform structure of graphene formed on silicon dioxide or porous silicon secondary particles.
[0103] The composite negative electrode active material 100 may include a first carbonaceous coating 150 disposed on the silicon-containing composite structure 30. The first carbonaceous coating 150 may be used to further improve the physical stability of the silicon-containing composite structure 30 and more effectively prevent side reactions between silicon and the electrolyte during cycling. The first carbonaceous coating 150 may include a first amorphous carbon 140a. The first carbonaceous coating 150 may include a high density of the first amorphous carbon 140a. The first amorphous carbon 140a may include, for example, polymer carbide, pitch carbon, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, carbon fiber, or a mixture thereof. The first carbonaceous coating 150 may further include crystalline carbon. Further including crystalline carbon in the first carbonaceous coating 150 may more effectively achieve a buffering effect on the volume change of the silicon-containing composite structure. The crystalline carbon may be, for example, natural graphite, artificial graphite, graphene, fullerene, carbon nanotube, or a mixture thereof.
[0104] The composite negative electrode active material 100 may include a second amorphous carbon 140b disposed within the silicon-containing composite structure 30. The silicon-containing composite structure 30 may include porous silicon secondary particles 20, and the second amorphous carbon 140b may be disposed within the pores of the porous silicon secondary particles 20. The second amorphous carbon 140b may be disposed between a plurality of silicon composite primary particles 10 that make up the porous silicon secondary particles 20. The silicon composite primary particles 10 may include, for example: silicon 110; suboxides of silicon 130 (SiO x , 0 < x < 2), disposed on the silicon 110; a second carbon sheet 120b, disposed on the suboxides of silicon 130; and a second amorphous carbon 140b, disposed on the second carbon sheet 120b. Since the pores inside the silicon-containing composite structure 30 are densely filled with the second amorphous carbon 140b, the silicon-containing composite structure 30 may have a dense cluster with a non-porous structure. Since the silicon-containing composite structure 30 has such a non-porous structure, side reactions with the electrolyte during cycling may be further reduced, and the volume change of silicon may be more effectively alleviated. The second amorphous carbon 140b may include, for example, polymer carbide, pitch carbon, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, carbon fiber, or a mixture thereof.
[0105] When the carbon in the first carbon sheet 120a and the carbon in the second carbon sheet 120b are collectively referred to as the first carbon, and the carbon in the first amorphous carbon 140a and the carbon in the second amorphous carbon 140b are collectively referred to as the second carbon, the mixing ratio of the total weight of the first carbon to the total weight of the second carbon in the silicon-containing composite structure 30 may be, for example, about 30:1 to about 1:3, about 20:1 to about 1:1, or about 10:1 to about 1:0.9. Since the mixing ratio of the first carbon to the second carbon is within the above range, a lithium battery with improved cycle characteristics can be provided. The mixing ratio of the first carbon to the second carbon may be determined by thermogravimetric analysis. The first carbon may be associated with a peak appearing in a region between about 700°C and about 750°C, and the second carbon may be associated with a peak appearing in a region between about 600°C and about 650°C. Thermogravimetric analysis may be performed, for example, in an ambient atmosphere at a temperature rise rate of about 10°C / min in a range of about 25°C to about 1,000°C. For example, the first carbon may be crystalline carbon, and, for example, the second carbon may be amorphous carbon.
[0106] The composite negative active material 100 may have, for example, a non-spherical shape. The silicon-containing composite structure 30 may have, for example, a circularity of 0.9 or less. The silicon-containing composite structure 30 may have, for example, a circularity of about 0.7 to about 0.9, about 0.8 to about 0.9, or about 0.85 to about 0.9. For example, the circularity may be defined as 4πA / P 2 (A stands for area and P stands for perimeter).
[0107] The composite negative electrode active material 100 may have a thickness of, for example, about 1 m 2 / g to about 20m 2 / g, about 3m 2 / g to about 18m 2 / g, or about 5m 2 / g to about 15m 2 When the composite negative electrode active material has a specific surface area within this range, a lithium battery using the composite negative electrode active material may have further improved cycle characteristics.
[0108] The silicon composite primary particles 10 may include: silicon 110; silicon 20 oxide 130 (SiO x, (0 < x < 2), disposed on at least one surface of the silicon; and a second carbon sheet 120b, disposed on one surface of the silicon suboxide. The silicon 110 may have, for example, an eutectic shape, a needle shape, a spherical shape, or a combination thereof. The silicon 110 may have any suitable shape and is not limited to any particular form. For example, the silicon 110 may be in the form of, for example, a sphere, a nanowire, a needle, a rod, a particle, a nanotube, a nanorod, a wafer, a nanoribbon, or a combination thereof. The silicon may have an average size of about 10 nm to about 1,000 nm, about 10 nm to about 500 nm, about 20 nm to about 300 nm, or about 50 nm to about 200 nm. When the silicon is a spherical particle, the average size of the silicon may refer to the average particle diameter, or if the silicon is a non-spherical particle (e.g., an eutectic particle or a needle-shaped particle), the average size of the silicon may refer to the major axis length, the length, or the thickness. In the silicon composite primary particle 10, the silicon suboxide 130 (SiO x , (0 < x < 2) may be placed to cover at least one surface of the silicon. The silicon suboxide 130 may be directly disposed on the silicon 110. The silicon suboxide 130 may completely or partially cover the surface of the silicon 110. The coverage rate of the silicon suboxide 130 may be, for example, about 1% to 100%, about 5% to about 99%, about 10% to about 95%, or about 20% to about 90% with respect to the total surface area of the silicon 110.
[0109] Refer to Figure 1c and Figure 1d, the composite negative electrode active material 100 may further include a second carbon-based coating 160 disposed on the first carbon-based coating 150. The composite negative electrode active material 100 may include: a silicon-containing composite structure 30; a first carbon-based coating 150 disposed on the silicon-containing composite structure 30; and a second carbon-based coating 160 disposed on the first carbon-based coating 150. The second carbon-based coating 160 may further improve the physical stability of the silicon-containing composite structure 30 and more effectively prevent side reactions between silicon 110 and the electrolyte during cycling. The second carbon-based coating 160 may include a third amorphous carbon 140c. The second carbon-based coating 160 may include a third amorphous carbon 140c having a high density. The third amorphous carbon 140c may not include a heterogeneous element belonging to at least one of Groups 15 and 17 selected from the periodic table. Therefore, the second carbon-based coating 160 may not contain a heterogeneous element. That is, the third amorphous carbon 140c may not contain a heterogeneous element. The third amorphous carbon 140c may include, for example, asphalt carbon, soft carbon, hard carbon, mesophase asphalt carbide, calcined coke, carbon fiber or a mixture thereof. The second carbon-based coating 160 may also include crystalline carbon. Further including crystalline carbon in the second carbon-based coating 160 may achieve a more effective buffering of the volume change of the silicon-containing composite structure 30. Crystalline carbon may be, for example, natural graphite, artificial graphite, graphene, fullerene, carbon nanotube or a mixture thereof. The third amorphous carbon 140c may include, for example, asphalt carbon, soft carbon, hard carbon, mesophase asphalt carbide, calcined coke, carbon fiber or a mixture thereof.
[0110] The composite negative electrode active material 100 including the second carbon-based coating 160 may have, for example, a spherical shape. The composite negative electrode active material 100 including the second carbon-based coating 160 may have, for example, a circularity of 0.9 or greater. The circularity of the composite negative electrode active material 100 including the second carbon-based coating 160 may be, for example, about 0.9 to about 0.99, about 0.9 to about 0.98, or about 0.9 to about 0.95. For example, the circularity may be defined as 4πA / P 2 (A stands for area and P stands for perimeter).
[0111] The composite negative electrode active material 100 including the second carbon-based coating layer 160 may have a thickness of, for example, about 1 m 2 / g to about 10m 2 / g, about 2m 2 / g to about 9m 2 / g, or about 4m 2 / g to about 8m 2 Since the composite negative electrode active material 100 including the second carbon-based coating layer 160 has a specific surface area within the above range, the cycle characteristics of the lithium battery using the composite negative electrode active material 100 can be further improved.
[0112] Reference Figure 1a to Figure 1d , the composite negative electrode active material 100 may have an average particle size (D50) of, for example, about 1 μm to about 10 μm, about 3 μm to about 10 μm, or about 5 μm to about 10 μm. The composite negative electrode active material 100 may have a particle size (D10) of, for example, about 0.1 μm to about 7 μm, about 0.5 μm to about 7 μm, or about 1 μm to about 7 μm. The composite negative electrode active material 100 may have a particle size (D90) of, for example, about 10 μm to about 30 μm, about 10 μm to about 27 μm, or about 10 μm to about 25 μm. Since the composite negative electrode active material 100 has an average particle size (D50), particle size (D10) and / or particle size (D90) within the above range, further improvement in the cycle characteristics of a lithium battery using the composite negative electrode active material can be achieved.
[0113] The composite negative electrode active material 100 may include a silicon-containing composite structure 30, and may further include a lithium compound disposed within the silicon-containing composite structure 30. For example, since the composite negative electrode active material 100 undergoes cycling after being assembled into a lithium battery, the composite negative electrode active material 100 may further include such a lithium compound derived from a heterogeneous element therein. Since the composite negative electrode active material 100 also includes such a lithium compound, a reduction in the internal resistance of a lithium battery including the composite negative electrode active material 100 may be achieved, and an improvement in the cycle characteristics of the lithium battery may be achieved. The lithium compound may be, for example, a lithium salt, lithium oxide, lithium nitride, lithium oxynitride, lithium phosphate, and the like. The lithium compound may include, for example, at least one selected from LiF and Li2O.
[0114] A negative electrode according to another embodiment may include the composite negative electrode active material. Since the negative electrode includes the composite negative electrode active material, improved cycle characteristics and reduced volume change may be achieved.
[0115] For example, the negative electrode may be prepared by a wet process. The negative electrode may be prepared by the method described below as an example; however, the method for preparing the negative electrode is not necessarily limited thereto and may be adjusted according to desired conditions.
[0116] First, the negative electrode active material composition can be prepared by mixing the above-mentioned negative electrode active material, conductive material, binder and solvent. The prepared negative electrode active material composition can be directly coated on a copper current collector and dried to produce a negative electrode plate having a negative electrode active material layer formed on a copper current collector. Alternatively, the negative electrode active material composition can be cast on a separate support, and the film stripped from the support can be laminated on the copper current collector to form a negative electrode plate having a negative electrode active material layer formed on the copper current collector. The negative electrode collector may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. For example, the polymer may be a thermoplastic polymer. For example, the polymer may include polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI) or a combination thereof. The polymer may be an insulating polymer. Since the base film includes an insulating thermoplastic polymer, the base film softens or liquefies and blocks the operation of the battery in the case of a short circuit, thereby preventing a rapid increase in current. For example, the metal layer may include copper (Cu), stainless steel (SUS), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative electrode current collector may also include a metal sheet and / or a lead tab. For details of the base film, metal layer, metal sheet, and lead tab of the negative electrode current collector, reference may be made to the description of the positive electrode current collector provided below. Since the negative electrode current collector has the above structure, the weight of the negative electrode can be reduced, and as a result, the energy density of the negative electrode and the lithium battery can be improved.
[0117] Examples of the conductive material may include carbon black, graphite powder, natural graphite, artificial graphite, acetylene black, ketjen black and carbon fiber, carbon nanotubes; metal powders, metal fibers or metal tubes such as copper, nickel, aluminum, silver, etc.; and conductive polymers such as polyphenylene derivatives, etc. However, the conductive material is not limited to the aforementioned components, but may be any material that can be used as a conductive material in the art.
[0118] Examples of the binder may include vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), a mixture of the above polymers, styrene butadiene rubber-based polymers, polyacrylic acid, lithium-substituted polyacrylic acid, polyamide-imide, polyimide, etc. However, the binder is not limited to the aforementioned examples, and may be any binder available in the art.
[0119] Examples of the solvent may include N-methylpyrrolidone (NMP), acetone, water, and the like, but the solvent is not limited to the foregoing examples and may be any solvent available in the art.
[0120] It is also possible to generate pores inside the electrode plate by further adding a plasticizer and a pore former to the negative electrode active material composition.
[0121] The amount of each of the negative electrode active material, conductive material, binder and solvent used in the negative electrode can be at a level commonly used in lithium batteries. Depending on the intended use and configuration of the lithium battery, one or more of the conductive material, binder and solvent can be omitted.
[0122] Relative to the total weight of the negative electrode active material layer, the amount of the binder included in the negative electrode may be, for example, about 0.1 wt% to about 10 wt%, or about 0.1 wt% to about 5 wt%. Relative to the total weight of the negative electrode active material layer, the amount of the conductive material included in the negative electrode may be, for example, about 0.1 wt% to about 10 wt%, or about 0.1 wt% to about 5 wt%. Relative to the total weight of the negative electrode active material layer, the amount of the composite negative electrode active material included in the negative electrode may be about 0.1 wt% to about 99 wt%, about 0.1 wt% to about 90 wt%, about 0.1 wt% to about 50 wt%, about 0.1 wt% to about 30 wt%, about 0.1 wt% to about 20 wt%, or about 0.1 wt% to about 10 wt%.
[0123] In addition to the above-mentioned composite negative electrode active material, the negative electrode may also include other known negative electrode active materials.
[0124] For example, the negative electrode active material may include one or more selected from lithium metal, metals alloyable with lithium, transition metal oxides, non-transition metal oxides, and carbonaceous materials, but is not limited to the foregoing examples, and may be any negative electrode active material that can be used for lithium batteries in the art.
[0125] Examples of metals that can be alloyed with lithium may include Si, Sn, Al, Ge, Pb, Bi, Sb, Si-X alloys (wherein X is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth metal, or a combination thereof, but not Si), Sn-X alloys (wherein X is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth metal, or a combination thereof, but not Sn), etc. For example, X may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.
[0126] Examples of the transition metal oxide may include lithium titanium oxide, vanadium oxide, lithium vanadium oxide, and the like.
[0127] Examples of non-transition metal oxides may include SnO 2 and the like.
[0128] Examples of carbonaceous materials may include crystalline carbon, amorphous carbon, or mixtures thereof. Examples of crystalline carbon may include graphite, such as artificial graphite or natural graphite in amorphous form, plate form, sheet form, spherical form, or fiber form. Examples of amorphous carbon may include soft carbon (low temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0129] The total amount of the composite negative electrode active material and other conventional negative electrode active materials included in the negative electrode may be about 80 wt % to about 99 wt %, about 90 wt % to about 99 wt %, or about 90 wt % to about 95 wt % relative to the total weight of the negative electrode active material layer.
[0130] Alternatively, the negative electrode may be a dry negative electrode prepared by a dry process.
[0131] The dry negative electrode may include a composite negative electrode active material, a dry conductive material, and a dry binder.
[0132] The method for preparing a dry negative electrode may include, for example: preparing a dry mixture by dry mixing a composite negative electrode active material, a dry conductive material and a dry binder; providing a negative electrode collector; setting an intermediate layer on one side of the negative electrode collector; and setting the dry mixture on the intermediate layer and then rolling, thereby preparing a negative electrode having a negative electrode active material layer set on one surface of the negative electrode collector.
[0133] First, a dry mixture can be prepared by dry mixing a composite negative electrode active material, a dry conductive material, and a dry binder. The term "dry mixing" may refer to a process of mixing in the absence of a process solvent. The process solvent may be, for example, a solvent used in the preparation of an electrode slurry. For example, the process solvent may be water, NMP, etc., but is not limited thereto, and may be any process solvent for preparing an electrode slurry. Dry mixing may be performed using an agitator at a temperature of, for example, about 25°C to about 65°C. Dry mixing may be performed using an agitator at a speed of, for example, about 10 rpm to about 10,000 rpm, or about 100 rpm to about 10,000 rpm. Dry mixing may be performed using an agitator for, for example, about 1 minute to about 200 minutes, or about 1 minute to about 150 minutes. The composite negative electrode active material may be a dry composite negative electrode active material.
[0134] For example, dry mixing can be performed one or more times. First, a first mixture can be prepared by a first dry mixing of a dry composite negative active material, a dry conductive material, and a dry binder. The first dry mixing can be performed, for example, at a temperature of about 25°C to about 65°C at a rotation speed of 2,000rpm or less for 15 minutes or less. For example, the first dry mixing can be performed at a temperature of about 25°C to about 65°C at a rotation speed of about 500rpm to about 2,000rpm for about 5 minutes to about 15 minutes. Through the first dry mixing, the dry composite negative active material, the dry conductive material, and the dry binder can be uniformly mixed. Next, a second mixture can be prepared by a second dry mixing of the dry composite negative active material, the dry conductive material, and the dry binder. For example, a second dry mixing can be performed at a temperature of about 25°C to about 65°C at a rotation speed of 9,000rpm or less for 60 minutes or less. For example, the second dry mixing may be performed at a temperature of about 25° C. to about 65° C. and a rotation speed of about 4,000 rpm to about 9,000 rpm for about 10 minutes to about 60 minutes. Through the second dry mixing, a dry mixture containing a fibrillated dry binder may be obtained.
[0135] The agitator may be, for example, a kneader. The agitator may include, for example: a chamber; at least one rotating shaft rotatably disposed inside the chamber; and blades rotatably coupled to the rotating shaft and arranged along the longitudinal direction of the rotating shaft. The blades may be, for example, one or more selected from a ribbon blade, a sigma blade, a Z-type blade, a dispersion blade, and a spiral blade. By including the blades, a dough-like mixture can be prepared by effectively mixing a dry negative electrode composite active material, a dry conductive material, and a dry binder even without a solvent.
[0136] The prepared dry mixture can be introduced into an extrusion device and extruded into a sheet form. The pressure during extrusion can be, for example, about 4 MPa to about 100 MPa, or about 10 MPa to about 90 MPa. The extruded product obtained in the form of a sheet can be a negative electrode active material layer sheet.
[0137] Examples of dry conductive materials may include: carbon black, graphite powder, natural graphite, artificial graphite, acetylene black, ketjen black and carbon fiber, carbon nanotubes; metal powders, metal fibers or metal tubes such as copper, nickel, aluminum, silver, etc.; and conductive polymers such as polyphenylene derivatives, etc. However, the dry conductive material is not limited to the aforementioned components, but may be any material that can be used as a conductive material in the art. The conductive material may be, for example, a carbon-based conductive material. The dry conductive material may be a conductive material that is not in contact with a process solvent.
[0138] Examples of dry binders may include vinylidene fluoride / hexafluoropropylene copolymers, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the aforementioned polymers, styrene butadiene rubber polymers, etc. However, the dry binder is not necessarily limited to the aforementioned examples, but may be any dry binder available in the art. Examples of dry binders may include polytetrafluoroethylene (PTFE). The dry binder may be a binder that does not come into contact with a process solvent.
[0139] It is also possible to generate pores inside the negative electrode active material layer by further adding a plasticizer and a pore former to the dry mixture.
[0140] The amounts of the dry composite negative electrode active material, the dry conductive material and the dry binder used in the negative electrode active material layer may be in the same ranges as those of the composite negative electrode active material, the conductive material and the binder in the wet negative electrode.
[0141] Next, a negative electrode current collector may be provided. The negative electrode current collector may be, for example, an aluminum foil or a copper foil. For example, the negative electrode current collector may include a base film and a metal layer disposed on one or both sides of the base film. For example, the base film may include a polymer. For example, the polymer may be a thermoplastic polymer. For example, the polymer may include polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. Since the base film includes an insulating thermoplastic polymer, the base film softens or liquefies and blocks the operation of the battery in the case of a short circuit, thereby preventing a rapid increase in current. For example, the metal layer may include copper (Cu), stainless steel (SUS), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative electrode current collector may also include a metal sheet and / or a lead tab. For details of the base film, metal layer, metal sheet, and lead tab of the negative electrode current collector, reference may be made to the description of the positive electrode current collector provided below. Since the negative electrode current collector has the above structure, the weight of the negative electrode can be reduced, and as a result, the energy density of the negative electrode and the lithium battery can be improved.
[0142] Next, an intermediate layer may be disposed on at least one surface of the negative electrode current collector. The intermediate layer may include a carbon-based conductive material and a binder. The intermediate layer may be omitted.
[0143] Next, the prepared negative electrode active material layer sheet can be placed on the intermediate layer and then rolled to prepare a negative electrode having a negative electrode active material layer disposed on one surface of the negative electrode current collector. The intermediate layer can be disposed between the negative electrode current collector and the negative electrode active material layer. The rolling can be performed by, for example, roller pressing, flat pressing, etc., but is not necessarily limited thereto. The pressure during rolling is not limited to any particular range, but can be, for example, about 0.1 ton / cm 2 To about 10.0 ton / cm 2 If the pressure during rolling is excessively increased, cracks in the negative electrode current collector may be caused. If the pressure during rolling is too low, the bonding strength between the negative electrode current collector and the negative electrode active material layer may deteriorate.
[0144] A lithium battery according to another embodiment uses a negative electrode comprising the above-mentioned composite negative electrode active material.
[0145] By adopting a negative electrode including the above-mentioned composite negative electrode active material, a lithium battery can provide improved cycle characteristics.
[0146] The lithium battery may be prepared by the exemplary method described below, but the method is not necessarily limited thereto and may be adjusted according to desired conditions.
[0147] First, the negative electrode can be prepared by the method for preparing the negative electrode described above.
[0148] Next, a positive electrode active material composition can be prepared, the positive electrode active material composition comprising a mixture of a positive electrode active material, a conductive material, a binder and a solvent. The positive electrode active material composition can be directly coated on an aluminum current collector and dried to form a positive plate. Alternatively, the positive electrode active material composition can be cast on a separate support, and the film peeled off from the support can be laminated on the aluminum current collector to form a positive plate.
[0149] The positive electrode active material may be a lithium-containing metal oxide, and any lithium-containing metal oxide commonly used in the art may be utilized without limitation. Examples of positive electrode active materials may include one or more selected from composite oxides of lithium and metals selected from cobalt, manganese, nickel, and combinations thereof. The positive electrode active material may include at least one selected from the group consisting of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide. However, the positive electrode active material is not necessarily limited to the aforementioned components, but may be any positive electrode active material for lithium batteries available in the art.
[0150] For example, the positive electrode active material may be a compound represented by any of the following chemical formulas: Li a A 1-b B bD2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b B b O 2-c D c (where 0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05); LiE 2-b B b O 4-c D c (where 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b B c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Co b B c O 2-α F α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Co b B c O 2-α F2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b B c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Mn b B c O 2-α F α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b B c O 2-α F2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni b E c G dO2 (wherein 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5 and 0.001≤d≤0.1); Li a Ni b Co c Mn d GeO2 (wherein, 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0.001≤e≤0.1); Li a NeG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn b O4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiIO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2); and LiFePO4.
[0151] In the above formula, A can be Ni, Co, Mn or a combination thereof; B can be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D can be O, F, S, P or a combination thereof; E can be Co, Mn or a combination thereof; F can be F, S, P or a combination thereof; G can be Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q can be Ti, Mo, Mn or a combination thereof; I can be Cr, V, Fe, Sc, Y or a combination thereof; and J can be V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0152] Compounds with a coating added to the surface of the above compounds can also be used. In addition, mixtures of the above compounds and compounds with a coating added thereto can also be used. The coating added to the surface of the above compounds can include, for example, compounds of coating elements such as oxides and hydroxides of coating elements, hydroxyoxides of coating elements, carbonate oxides of coating elements, and hydroxycarbonates of coating elements. The compounds forming the above coating can be amorphous or crystalline. The coating elements included in the coating layer can be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method for forming the coating can be selected from methods that do not have an adverse effect on the physical properties of the positive electrode active material. Examples of coating methods can include spraying, dip coating, etc. Specific coating methods are well known to those of ordinary skill in the art, and therefore, detailed descriptions thereof will be omitted here.
[0153] For example, as the positive electrode active material, LiNiO2, LiCoO2, LiMn x O 2x (x = 1, 2), LiNi 1-x Mn x O2(0 < x < 1), LiNi 1-x-y Co x Mn y O2(0 ≤ x ≤ 0.5, 0 ≤ y ≤ 0.5), LiFeO2, V2O5, TiS, MoS, etc. can be used.
[0154] Examples of the positive electrode active material can include Li a Ni x Co y M z O 2-b A b (1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 ≤ y ≤ 0.3, 0 < z ≤ 0.3 and x + y + z = 1, where M is at least one selected from the group consisting of manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), and boron (B), and A is F, S, Cl, Br, or a combination thereof), LiNi x Co y Mn z O2(0.8 ≤ x ≤ 0.95, 0 < y ≤ 0.2, 0 < z ≤ 0.2 and x + y + z = 1), LiNi x Co y Al zO2 (0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2 and x + y + z = 1), LiNi x Co y Al v Mn w O2 (0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < v ≤ 0.2, 0 < w ≤ 0.2 and x + y + v + w = 1), Li a Ni x Mn y M' z O 2-b A b (1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0 < x ≤ 0.3, 0.5 ≤ y < 1, 0 < z ≤ 0.3 and x + y + z = 1, where M' is cobalt (Co), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and A is F, S, Cl, Br or a combination thereof), etc.
[0155] The positive electrode active material composition may use the same conductive material, binder, and solvent as those used in the negative electrode active material composition. In addition, a plasticizer may be further added to the positive electrode active material composition and / or the negative electrode active material composition to form pores in the electrode plate.
[0156] The amounts of the positive electrode active material, conductive material, binder, and solvent may be at levels commonly used in lithium batteries. Depending on the intended use purpose and structure of the lithium battery, one or more of the conductive material, binder, and solvent may be omitted.
[0157] Relative to the total weight of the positive electrode active material layer, the amount of the binder included in the positive electrode may be, for example, about 0.1wt% to about 10wt%, or about 0.1wt% to about 5wt%. Relative to the total weight of the positive electrode active material layer, the amount of the conductive material included in the positive electrode may be, for example, about 0.1wt% to about 10wt%, or about 0.1wt% to about 5wt%. Relative to the total weight of the positive electrode active material layer, the amount of the positive electrode active material included in the positive electrode may be, for example, about 70wt% to about 99wt%, about 90wt% to about 99wt%, or about 95wt% to about 99wt%. For example, the positive electrode current collector may utilize a plate, foil, etc. composed of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof. For example, the positive current collector may have a thickness of about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 5 μm to about 25 μm, or about 10 μm to about 20 μm. The positive current collector may include, for example, a substrate film and a metal layer disposed on one or both sides of the substrate film. The substrate film may include, for example, a polymer. For example, the polymer may be a thermoplastic polymer. For example, the polymer may include polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. For example, the polymer may be an insulator. Since the substrate film includes an insulating thermoplastic polymer, the substrate film softens or liquefies and blocks the operation of the battery in the case of a short circuit, thereby preventing a rapid increase in current. For example, the metal layer may include indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The metal layer can be used as an electrochemical fuse by disconnecting in the case of overcurrent, thereby providing protection against short circuit. The limiting current and peak current can be controlled by controlling the thickness of the metal layer. The metal layer can be plated or deposited on the substrate film. As the thickness of the metal layer decreases, the limiting current and / or peak current of the positive electrode current collector decreases, and therefore, the stability of the lithium battery can be improved in the case of a short circuit. A lead tab can be added to the metal layer for external connection. The lead tab can be welded to the metal layer or the metal layer / substrate film laminate by ultrasonic welding, laser welding, spot welding, etc. When the substrate film and / or the metal layer melts during welding, the metal layer can be electrically connected to the lead tab. In order to further ensure the welding between the metal layer and the lead tab, a metal sheet can be added between the metal layer and the lead tab. The metal sheet can be a sheet of the same material as the metal of the metal layer. For example, the metal sheet can be a metal foil, a metal mesh, etc. For example, the metal sheet can be an aluminum foil, a copper foil, a SUS foil, etc.By welding the lead tab after placing the metal sheet on the metal layer, the lead tab can be welded to the metal sheet / metal layer laminate or the metal sheet / metal layer / base film laminate. When the base film, the metal layer and / or the metal sheet melt during welding, the metal layer or the metal layer / metal sheet laminate can be electrically connected to the lead tab. The metal sheet and / or the lead tab can be further added to a portion of the metal layer. For example, the base film can have a thickness of about 1 μm to about 50 μm, about 1.5 μm to about 50 μm, about 1.5 μm to about 40 μm, or about 1 μm to about 30 μm. When the base film has a thickness within the above range, the weight reduction of the electrode assembly can be more effectively achieved. For example, the base film can have a melting point of about 100°C to about 300°C, about 100°C to about 250°C, or about 100°C to about 200°C. Since the base film has a melting point within the above range, the base film can be melted and easily joined to the lead tab during the process of welding the lead tab. In order to improve the bonding strength between the base film and the metal layer, the base film can be subjected to surface treatment, such as corona treatment. For example, the metal layer can have a thickness of about 0.01 μm to about 3 μm, about 0.1 μm to about 3 μm, about 0.1 μm to about 2 μm, or about 0.1 μm to about 1 μm. When the metal layer has a thickness within the above range, the stability of the electrode assembly can be ensured while maintaining conductivity. For example, the metal sheet can have a thickness of about 2 μm to about 10 μm, about 2 μm to about 7 μm, or about 4 μm to about 6 μm. When the metal sheet has a thickness within the above range, the connection between the metal layer and the lead tab can be more easily performed. Since the positive current collector has the above structure, the weight of the positive electrode can be reduced, and as a result, the energy density of the positive electrode and the lithium battery can be improved.
[0158] Next, a separator located between the positive electrode and the negative electrode may be prepared.
[0159] The diaphragm can be any diaphragm commonly used in lithium batteries. For example, the diaphragm can be a diaphragm capable of retaining a large amount of electrolyte solution while exhibiting low resistance to ion migration in the electrolyte. For example, the diaphragm can be formed of a material in the form of a non-woven fabric or a woven fabric selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE) or a combination thereof. Lithium-ion batteries can use, for example, a rollable diaphragm formed of polyethylene, polypropylene, etc. Lithium-ion polymer batteries can use, for example, a diaphragm capable of retaining a large amount of organic electrolyte solution.
[0160] The separator can be prepared by the method described below as an example. However, the method for preparing the separator is not necessarily limited to this method, but can be adjusted according to required conditions.
[0161] First, a separator composition can be prepared by mixing a polymer resin, a filler and a solvent. The separator composition can be directly coated on the top of the electrode and dried to form a separator. Alternatively, the separator can be formed by casting the separator composition on a support and drying it, and then laminating the separator peeled from the support on the top of the electrode.
[0162] The polymer used to prepare the separator is not particularly limited, and any polymer that can be used as a binder for an electrode plate can be used. For example, the polymer can use vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or a mixture thereof.
[0163] Next, an electrolyte may be prepared. The electrolyte may be, for example, a liquid electrolyte, a solid electrolyte, a gel electrolyte, or any combination thereof.
[0164] The electrolyte may be, for example, an organic electrolyte solution. The organic electrolyte solution may be prepared by dissolving a lithium salt in an organic solvent.
[0165] For the organic solvent, any organic solvent available in the art can be used. Examples of organic solvents may include propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, and mixtures thereof.
[0166] As the lithium salt, any lithium salt available in the art may be used. Examples of lithium salts may include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (1≤x≤20 and 1≤y≤20), LiCl, LiI, or a mixture thereof.
[0167] Alternatively, the electrolyte may be a solid electrolyte. The solid electrolyte may be, for example, boron oxide, lithium oxynitride, etc., but is not limited thereto, and may be any solid electrolyte available in the art. For example, the solid electrolyte may be formed on the negative electrode by a method such as sputtering, or a separate solid electrolyte sheet may be stacked on the negative electrode.
[0168] The solid electrolyte can be, for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer solid electrolyte, or any combination thereof.
[0169] The electrolyte in solid state (or solid electrolyte) can be, for example, an oxide-based electrolyte in solid state. The oxide-based solid electrolyte can be at least one selected from the following: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 < x < 2 and 0 ≤ y < 3), BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT) (0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg3Nb 2 / 3 )O3 - PbTiO3 (PMN - PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3 (0 < x < 2 and 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1 and 0 < z < 3), Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 (0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), Li x La y TiO3 (0 < x < 2 and 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2, and Li 3+x La3M2O 12 (M = Te, Nb or Zr, and x is an integer from 1 to 10). The electrolyte in solid state can be prepared by a sintering method or the like. For example, the oxide-based solid electrolyte can be at least one selected from Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O12 A garnet-type solid electrolyte among (M-doped LLZO, where M = Ga, W, Nb, Ta, or Al, and x is an integer from 1 to 10).
[0170] Examples of sulfide-based solid-state electrolytes can include lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide, or combinations thereof. Sulfide-based solid-state electrolyte particles can include Li2S, P2S5, SiS2, GeS2, B2S3, or combinations thereof. Sulfide-based solid-state electrolyte particles can be Li2S or P2S5. It is known that sulfide-based solid-state electrolyte particles have a higher lithium-ion conductivity than the ionic conductivity of other inorganic compounds. For example, a sulfide-based solid-state electrolyte can include Li2S and P2S5. If the sulfide solid electrolyte material constituting the sulfide-based solid electrolyte includes Li2S-P2S5, the mixed molar ratio of Li2S and P2S5 can be in the range of, for example, about 50:50 to about 90:10. In addition, materials such as Li3PO4, halogens, halogen compounds, Li 2+2x Zn1- x GeO4 (“LISICON”, 0 ≤ x < 1), Li 3+y PO 4-x N x (“LIPON”, 0 < x < 4 and 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 S4 (“Thio-LISICON”) and Li2O-Al2O3-TiO2-P2O5 (“LATP”) can be added to inorganic solid electrolytes such as Li2S-P2S5, SiS2, GeS2, B2S3, or combinations thereof to prepare an inorganic solid electrolyte, and this inorganic solid electrolyte can be used as a sulfide solid electrolyte. Non-limiting examples of sulfide solid electrolyte materials can include: Li2S-P2S5; Li2S-P2S5-LiX (X = halogen element); Li2S-P2S5-Li2O; Li2S-P2S5-Li2O-LiI; Li2S-SiS2; Li2S-SiS2-LiI; Li2S-SiS2-LiBr; Li2S-SiS2-LiCl; Li2S-SiS2-B2S3-LiI; Li2S-SiS2-P2S5-LiI; Li2S-B2S3; Li2S-P2S5-Z m S n (0 < m < 10, 0 < n < 10, Z = Ge, Zn, or Ga); Li2S-GeS2; Li2S-SiS2-Li3PO4; and Li2S-SiS2-Li p MO q(0 < p < 10, 0 < q < 10, M = p, Si, Ge, B, Al, Ga or In). In this regard, the sulfide-based solid electrolyte material can be prepared by subjecting starting materials of the sulfide-based solid electrolyte material (e.g., Li2S, P2S5, etc.) to treatments such as melt quenching, mechanical grinding, etc. Further, a calcination process can be performed after the above treatments. The sulfide-based solid electrolyte can be amorphous or crystalline, or can be in their mixed state. For example, the polymer solid electrolyte can include a mixture of a lithium salt and a polymer, or can include a polymer having an ion-conducting functional group. For example, the polymer solid electrolyte can be a polymer electrolyte in a solid state at 25 °C and 1 atm. For example, the polymer solid electrolyte may not contain a liquid. The polymer solid electrolyte can include a polymer. For example, the polymer can be polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF), poly(methyl methacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), poly(ethylenedioxythiophene) (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), sulfonated poly(aryl ether ketone) (SPAEK), poly[bis(benzimidazolo benzophenanthroline)] (SPBIBI), poly(styrene sulfonate) (PSS), and lithium 9,10-diphenylanthracene-2-sulfonate (DPASLi + ), or a combination thereof. However, the polymer is not limited to the foregoing examples and can be any material available in the art for use in polymer electrolytes. The lithium salt can be any lithium salt available in the art. The lithium salt can be, for example, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1SO2) (x and y are each an integer from 1 to 20), LiCl, LiI or a mixture thereof. For example, the polymer included in the polymer solid electrolyte may be a compound comprising 10 or more repeating units, 20 or more repeating units, 50 or more repeating units, or 100 or more repeating units. For example, the polymer included in the polymer solid electrolyte may have a weight average molecular weight of 1,000 Daltons or greater, 10,000 Daltons or greater, 100,000 Daltons or greater, or 1,000,000 Daltons or greater. For example, the gel electrolyte may be a polymer gel electrolyte. For example, the gel electrolyte may have a gel state while not containing a polymer. For example, the polymer gel electrolyte may include a liquid electrolyte and a polymer, or may include an organic solvent and a polymer having an ion conductive functional group. For example, the polymer gel electrolyte may be a polymer electrolyte that is in a gel state at 25° C. and 1 atm. For example, the polymer gel electrolyte may have a gel state that does not contain a liquid. The liquid electrolyte used in the polymer gel electrolyte can be, for example, an ionic liquid, a mixture of a lithium salt and an organic solvent, a mixture of a lithium salt and an organic solvent, a mixture of an ionic liquid and an organic solvent, or a mixture of a lithium salt and an ionic liquid. The polymer used in the polymer gel electrolyte can be selected from the polymer used in the solid polymer electrolyte. The organic solvent can be selected from the organic solvent used in the liquid electrolyte. The lithium salt can be selected from the lithium salt used in the polymer solid electrolyte. The ionic liquid can refer to a room temperature molten salt composed solely of ions and having a melting point of room temperature or lower or a salt in a liquid state at room temperature. For example, the ionic liquid can be at least one selected from the compounds containing a and b: a) at least one cation selected from ammonium, pyrrolidinium, pyridinium, pyrimidinium, imidazolium, piperidinium, pyrazolium, oxazolium, pyridazinium, phosphonium, sulfonium, triazolium and mixtures thereof; and b) selected from BF4 - PF6 - 、AsF6 - 、SbF6 - 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - , Cl - Br - ,I - 、BF4 - 、SO4 - CF3SO3 - 、(FSO2)2N - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N- and (CF3SO2)2N - At least one anion in the lithium battery. For example, the polymer solid electrolyte can be formed into a polymer gel electrolyte by being immersed in a liquid electrolyte in a lithium battery. The polymer gel electrolyte may also include inorganic particles. For example, the polymer included in the polymer gel electrolyte may be a compound containing 10 or more repeating units, 20 or more repeating units, 50 or more repeating units, or 100 or more repeating units. For example, the polymer included in the polymer gel electrolyte may have a weight average molecular weight of 500 Daltons or more, 1,000 Daltons or more, 10,000 Daltons or more, 100,000 Daltons or more, or 1,000,000 Daltons or more.
[0171] Reference Figure 5 , the lithium battery 1 according to the embodiment may include a positive electrode 3, a negative electrode 2, and a separator 4. The positive electrode 3, the negative electrode 2, and the separator 4 may be wound or folded to form a battery structure 7. The formed battery structure 7 may be accommodated in a battery case 5. The battery case 5 may be injected with an organic electrolyte solution and sealed with a cap assembly 6, thereby completing the preparation of the lithium battery 1. The battery case 5 may have a cylindrical shape, but is not necessarily limited thereto, and may have a polygonal shape, a thin film shape, etc.
[0172] Reference Figure 6 , the lithium battery 1 according to the embodiment may include a positive electrode 3, a negative electrode 2 and a separator 4. The separator 4 may be disposed between the positive electrode 3 and the negative electrode 2, and the positive electrode 3, the negative electrode 2 and the separator 4 may be wound or folded to form a battery structure 7. The battery structure 7 may be housed in a battery case 5. An electrode tab 8 serving as an electrical path for guiding the current formed in the battery structure 7 to the outside may be included. The battery case 5 may be injected with an organic electrolyte solution and sealed, thereby completing the preparation of the lithium battery 1. The battery case 5 may have a polygonal shape, but is not necessarily limited thereto, and may also have, for example, a cylindrical shape, a thin film shape, and the like.
[0173] Reference Figure 7 , the lithium battery 1 according to the embodiment may include a positive electrode 3, a negative electrode 2 and a separator 4. The separator 4 may be disposed between the positive electrode 3 and the negative electrode 2 to form a battery structure. The battery structure 7 may be stacked into a dual-cell structure and then accommodated in a battery case 5. An electrode tab 8 may be included that serves as an electrical path for guiding the current generated in the battery structure 7 to the outside. The battery case 5 may be injected with an organic electrolyte solution and sealed, thereby completing the preparation of the lithium battery 1. The battery case 5 may have a polygonal shape, but is not necessarily limited thereto, and may also have, for example, a cylindrical shape, a thin film shape, and the like.
[0174] Pouch type lithium battery corresponds to Figure 6 and Figure 7 A lithium battery using a bag as a battery housing as shown in . A pouch-type lithium battery may include one or more battery structures. The battery structure may be formed by arranging a separator between the positive electrode and the negative electrode. The battery structure may be stacked into a dual-monobody structure, immersed in an organic electrolyte solution, and then contained and sealed in a bag, thereby completing the preparation of a pouch-type lithium battery. For example, although not shown in the accompanying drawings, the above-mentioned positive electrode, negative electrode, and separator may be simply stacked in the form of an electrode assembly and then contained in a bag, or may be wound or folded into a core-type electrode assembly and then contained in a bag. Subsequently, an organic electrolyte solution may be injected into the bag and then sealed, thereby completing the preparation of the lithium battery.
[0175] Lithium batteries can be used, for example, in electric vehicles (EVs) due to their excellent life characteristics and high rate capabilities. For example, lithium batteries can be used in hybrid vehicles, such as plug-in hybrid electric vehicles (PHEVs), etc. In addition, lithium batteries can be used in any field that requires a large amount of energy storage. For example, lithium batteries can be used in electric bicycles, power tools, etc.
[0176] Multiple units of lithium batteries can be stacked to form a battery module, and multiple units of a battery module can form a battery pack. Such a battery pack can be used for all types of devices that require high capacity and high output. For example, the battery pack can be used for laptop computers, smart phones, electric vehicles, etc. The battery module may include, for example, a plurality of batteries and a frame for holding the batteries. The battery pack may include, for example, a plurality of battery modules and bus bars connecting these battery modules. The battery module and / or the battery pack may also include a cooling device. Multiple battery packs may be controlled by a battery management system. The battery management system may include a battery pack and a battery control device connected to the battery pack.
[0177] According to another embodiment, a method for preparing a composite negative electrode active material may include: providing porous silicon secondary particles; preparing a silicon-containing composite structure by supplying a carbon source gas to the porous silicon secondary particles and performing a heat treatment on the porous silicon secondary particles; preparing a first composition, the first composition including a silicon-containing composite structure, an amorphous carbon precursor containing a heterogeneous element selected from Group 15 or Group 17 of the periodic table, and an additive; and preparing a composite negative electrode active material by heat-treating the first composition at a temperature of 350° C. or less. The composite negative electrode active material prepared by the above preparation method may include: a silicon-containing composite structure; a first carbon-based coating including a first amorphous carbon and disposed on the silicon-containing composite structure; and a second amorphous carbon disposed in the silicon-containing composite structure, wherein the silicon-containing composite structure may include porous silicon secondary particles and a first carbon sheet disposed on the porous silicon secondary particles, wherein the porous silicon secondary particles may each include an aggregate of a plurality of silicon composite primary particles, wherein the silicon composite primary particles may include silicon, silicon oxide (SiO x, (0 < x < 2), and a second carbon sheet disposed on the silicon suboxide, and wherein the second amorphous carbon may be disposed in the pores of the porous silicon secondary particles, and the second amorphous carbon may include a hetero element belonging to at least one of Group 15 and Group 17 selected from the periodic table of elements.
[0178] First, a process of setting the porous silicon secondary particles may be performed.
[0179] It can be formed by including silicon and silicon suboxide (SiO formed on the silicon x, the structure of (0 < x < 2) is pulverized to obtain pulverized silicon primary particles. The silicon primary particles can have, for example, a needle-like eutectic particle shape or a spherical particle shape. A composition can be obtained by mixing the pulverized silicon primary particles, a dispersant, and a solvent. Porous silicon secondary particles can be obtained from the obtained composition. Pores can be present inside the porous silicon secondary particles. The porous silicon secondary particles can have a porosity of, for example, about 0.1% to about 50%, about 1% to about 40%, or about 5% to about 30%. The pores in the porous silicon secondary particles can have a size of about 10 nm to about 500 nm, about 20 nm to about 200 nm, or about 30 nm to about 300 nm. The porous silicon secondary particles can be prepared from the above composition by any of various methods (e.g., co-precipitation, spray drying, or solid-phase methods). For example, the porous silicon secondary particles can be prepared by spray drying. When the porous silicon secondary particles are prepared by spray drying, their particle size can be controlled by appropriately selecting the spray type, the pressurized gas supply rate, the composition supply rate, the drying temperature, etc. Spray drying can be carried out at an atmospheric temperature of about room temperature (25 °C) to about 500 °C, for example, about 50 °C to about 300 °C, about 50 °C to about 250 °C, or about 70 °C to about 200 °C. When carried out within the above temperature range, spray drying can ensure that the prepared silicon composite secondary particles have an appropriate porosity while preventing problems such as particle agglomeration / blockage of the particle discharge outlet due to moisture condensation near the particle discharge outlet in advance. During spray drying, the spray pressure of the spray drying can be about 1 bar to about 5 bar, or about 0.3 MPa to about 0.6 MPa. During spray drying, for example, the size of the nozzle can be about 1 μm to about 10 μm, and can be 5 μm. Before spray drying, the surface area of the starting material can be increased as much as possible by pulverization, for example, as needed. For this purpose, pulverized silicon primary particles can be used as the starting material. For example, when formed by spray drying, the obtained porous silicon secondary particles can be spherical. A dispersant (e.g., stearic acid) can be partially retained on the surface of the porous silicon secondary particles. An alcohol can be used as the solvent. The alcohol can be, for example, ethanol, methanol, isopropanol, etc. When heat treatment is carried out using an alcohol solvent, the dispersant and the solvent can be removed together, thereby minimizing the amount of the dispersant remaining in the porous silicon composite. As a result, the obtained silicon-containing composite can have the least amount of oxygen remaining in the pores of the porous silicon secondary particles. The dispersant can be used to uniformly disperse the silicon primary particles. The dispersant can be, but is not limited to, at least one selected from stearic acid, resorcinol, polyvinyl alcohol, carbon pitch, and combinations thereof. The amount of the dispersant can be about 1 part by weight to about 15 parts by weight, for example, about 5 parts by weight to about 10 parts by weight, based on the total weight of the composition. When the amount of the dispersant is within these ranges, silicon and graphene can be uniformly dispersed without agglomeration.
[0180] Subsequently, a process of preparing a silicon-containing composite structure by supplying a carbon source gas to the porous silicon secondary particles and performing a heat treatment on the porous silicon secondary particles may be performed.
[0181] By supplying a carbon source gas to the porous silicon secondary particles and performing a heat treatment on the porous silicon secondary particles, a carbon sheet can be disposed on the porous silicon secondary particles, thereby preparing a porous silicon-containing composite. The carbon source gas can first fill the pores of the porous silicon secondary particles, and the carbon sheet can grow on the outside of the porous silicon secondary particles and the exposed surface of the silicon composite primary particles (i.e., the surface of the silicon composite primary particles defining the pores). The carbon source gas can be at least one selected from the compounds represented by the following formula 1, the compounds represented by the following formula 2, and the first oxygen-containing compound represented by the following formula 3.
[0182] Formula 1
[0183] C n H (2n+2-a) [OH] a
[0184] In Formula 1, n may be an integer of 1 to 20, 2 to 18, or 4 to 16, and a may be 0 or 1,
[0185] Formula 2
[0186] C n H (2n)
[0187] In Formula 2, n can be an integer from 2 to 6,
[0188] Formula 3
[0189] C x H y O z
[0190] In Formula 3, x may be an integer of 1 to 20, 2 to 18, or 4 to 16, y may be 0, an integer of 1 to 20, or an integer of 2 to 18, and z may be 1 or 2.
[0191] For example, the carbon source gas can be at least one selected from methane, ethylene, propylene, methanol, ethanol, propanol, and acetylene. The heat treatment can be carried out at a temperature of about 600 °C to about 1,100 °C (for example, at a temperature of about 650 °C to about 1,000 °C, or for example, at a temperature of about 700 °C to about 1,000 °C). Performing the heat treatment at a temperature within the above range can allow graphene to form at a high density on the core or shell or on both the core and the shell. When the carbon sheet is a carbon nanotube sheet, a carbon fiber sheet, a graphite carbon sheet, or a graphene oxide sheet, the carbon sheet can be prepared by a known method. The carbon sheet can include a first carbon sheet and a second carbon sheet. The first carbon sheet can grow on the outer surface of the porous silicon secondary particles. The second carbon sheet can grow on the exposed surface of the silicon composite primary particles.
[0192] The silicon-containing composite structure can include porous silicon secondary particles, and the porous silicon secondary particles can include an aggregate of a plurality of silicon composite primary particles.
[0193] The silicon composite primary particles can include, for example: silicon; silicon monoxide (SiO x , where 0 < x < 2), disposed on the silicon; and graphene (the second carbon sheet), disposed on the silicon monoxide. Silicon monoxide (SiO x , 0 < x < 2), being a material more unstable and oxygen-deficient than silicon dioxide (SiO2), has a tendency to react with other reactive materials (i.e., the carbon source gas) to form a more stable material. Utilizing this tendency, silicon monoxide (SiO x , 0 < x < 2) film can be used as a seed layer material to form graphene. The thickness of the silicon monoxide (SiO x , 0 < x < 2) film formed on the top of the silicon can seriously affect the shape, structure, etc. of the graphene. The thickness of the silicon monoxide (SiO x )(0 < x < 2) film can be changed, for example, by the composition of the carbon source gas required for graphene formation during the preparation process for forming graphene. The thickness of the silicon monoxide (SiO x )(0 < x < 2) film can be 300 μm or less. The thickness of the silicon monoxide (SiO x )(0 < x < 2) film can be, for example, 10 nm or less, about 0.1 nm to about 10 nm, about 0.1 nm to about 7.5 nm, about 0.1 nm to about 5 nm, or about 0.4 nm to about 5 nm. By using a silicon-containing composite structure including silicon composite primary particles having a silicon monoxide (SiO x )(0 < x < 2) film with a thickness within the above range, the capacity characteristics of the lithium battery can be further improved.
[0194] Next, a process of preparing a first composition including a silicon-containing composite structure, an amorphous carbon precursor including a heterogeneous element selected from Group 15 or Group 17 of the periodic table, and an additive may be performed.
[0195] The first composition can be prepared by dry mixing. Dry mixing can be carried out by a mixer of the type that performs mixing when there is no structure to apply physical force to the material being dry mixed inside the mixer. Such a mixer can be, for example, a planetary centrifugal mixer. A planetary centrifugal mixer can be a mixer that simultaneously performs rotational motion and orbital motion with or without vacuum conditions. For example, the rotation rate and the orbital rate can be independently 2,000 revolutions per minute (rpm) or less, or 1,000rpm or less. The structure that applies physical force to the material can point to the structure that applies force such as impact force to the material, for example, a rotor and a ball. Using the above-mentioned mixer can minimize the damage and change to the material being dry mixed.
[0196] For example, the planetary centrifugal mixer can be a planetary mixer or a planetary distributor mixer. For example, the planetary centrifugal mixer can be commercially available, for example, under the trade name Thinky Mixer (Thinky Company). Using a planetary centrifugal mixer as a mixer, by appropriately controlling the revolution rate and the rotation rate, the stirring process and the degassing process can be alternately performed to ensure the uniform mixing of the components. In the stirring process, the revolution rate can be 1,000rpm or less, for example, 900rpm or less, or for example, 750rpm or less, and the rotation rate can be 1,000rpm or less. In addition, in the degassing process, the revolution rate can be 2,000rpm or less, for example, 1,750rpm or less, or for example, 1,500rpm or less, and the rotation rate can be 100rpm or less, for example, about 10rpm to about 100rpm. When the revolution rate and the rotation rate are within the above range in the stirring process and the degassing process, the damage and change to each component can be minimized, and the uniform mixing of the components can be achieved.
[0197] In the dry mixing process, by introducing each component in multiple separate parts (e.g., 3 or 4 parts) rather than introducing all the components at once, more efficient penetration of carbon into the pores of the silicon composite can be achieved. In addition, using a mixer of the above type can allow the formation of a dense structure with amorphous carbon filled inside the silicon composite while maintaining the shape of the silicon composite.
[0198] Additives can be used to ensure uniform mixing during the dry mixing process, wherein the example of such additives can include N-methyl pyrrolidone, isopropyl alcohol (IPA), dimethylformamide, butanol or a combination thereof. Adding such additives during the dry mixing process can promote the dissolution of components (e.g., amorphous carbon precursors containing heterogeneous elements) and the subsequent penetration of these components. These additives can also enhance the bonding strength between components and are removed due to their high volatility. Relative to 100 parts by weight of the material being dry mixed, the amount of the additive can be, for example, 25 parts by weight or less, about 10 parts by weight to about 25 parts by weight, or about 12 parts by weight to about 25 parts by weight. Different from the above-mentioned dry mixing process, relative to 100 parts by weight of the material being wet mixed, the wet mixing process can involve additives of an amount greater than 25 parts by weight, about 26 parts by weight to about 150 parts by weight, about 30 parts by weight to about 150 parts by weight, or about 50 parts by weight to about 125 parts by weight. The amount of the additive in the first composition may be 25 parts by weight or less, about 5 parts by weight to about 25 parts by weight, about 10 parts by weight to about 25 parts by weight, or about 12 parts by weight to about 25 parts by weight, relative to the total weight of the solid content of 100 parts by weight of the first composition. The solid content of the second composition may include a silicon-containing composite structure and an amorphous carbon precursor containing a heterogeneous element selected from Group 15 or Group 17 of the periodic table. Dry mixing may be subjected to a process in which the temperature is controlled at 25°C or less or in a range of about 15°C to about 25°C. Alternatively, dry mixing may be performed at a temperature of about 30°C to about 80°C, about 50°C to about 80°C, or about 60°C to about 70°C.
[0199] The amorphous carbon precursor containing a heterogeneous element selected from Group 15 or Group 17 of the periodic table can be, for example, a fluorine-containing polymer, a nitrogen-containing polymer, a phosphorus (P)-containing polymer, or a mixture thereof. The fluorine-containing polymer can be, for example, polyvinylidene fluoride, polytetrafluoroethylene, etc. The nitrogen-containing polymer can be a polyamide, a polyimide, etc. The phosphorus (P)-containing polymer can be a polyphosphonic acid, etc.
[0200] In the first composition, the amount of the amorphous carbon precursor containing a heterogeneous element selected from Group 15 or Group 17 in the periodic table can be about 1 part by weight to about 75 parts by weight, about 3 parts by weight to about 60 parts by weight, or 5 parts by weight to 30 parts by weight, relative to 100 parts by weight of the first composition. When carried out under the above conditions, the amorphous carbon precursor can be more effectively infiltrated into the silicon-containing composite structure. When the amorphous carbon precursor is effectively infiltrated into the silicon-containing composite structure, the composite negative electrode active material prepared thereby can suppress the side reactions caused by the electrolyte after cycling, and can also achieve excellent properties regarding the physical volume expansion rate.
[0201] Next, the first composition may be heat-treated at 300° C. or less to prepare a composite negative active material.
[0202] By performing heat treatment on a first composition, amorphous carbon containing a hetero element selected from Group 15 or Group 17 of the periodic table can be formed from an amorphous carbon precursor containing a hetero element selected from Group 15 or Group 17 of the periodic table. Accordingly, the second amorphous carbon can be disposed within the silicon-containing composite structure, and the second amorphous carbon can include a hetero element belonging to at least one of Group 15 and Group 17 of the periodic table. The heat treatment of the first composition can be performed at a temperature of 350 °C or lower in an inert gas atmosphere. For example, the heat treatment of the first composition can be performed at a temperature of about 100 °C to about 350 °C, about 100 °C to about 300 °C, or about 100 °C to about 250 °C. If the temperature of the heat treatment is too high, the hetero element may evaporate during the heat treatment and thus cannot be retained in the amorphous carbon. The heat treatment can be performed in an inert atmosphere. The inert atmosphere can be an inert gas atmosphere. Examples of the inert gas can include nitrogen, argon, and the like.
[0203] The inventive concept will be described in more detail below through examples and comparative examples. However, it will be understood that the following examples are provided only for illustrating the inventive concept and should not be construed as limiting the scope of the inventive concept.
[0204] (Preparation of Composite Anode Active Material)
[0205] Comparative Example 1: Porous Silicon Secondary Particles
[0206] By pulverizing acicular silicon, acicular co-silicon particles are obtained, which have a length of about 120 nm and a thickness of about 30 nm and have a silicon suboxide (SiO x , 0 < x < 2) film formed on their surfaces.
[0207] A composition containing 30 parts by weight of acicular co-silicon particles, 10 parts by weight of stearic acid, and 60 parts by weight of isopropyl alcohol is prepared. By spray-drying the prepared composition and drying the spray-dried product, porous silicon secondary particles with an average particle size of about 5 μm are obtained.
[0208] The spray-drying is performed using a spray dryer (Micro Mist Spray Dryers, Fuji Electric Co., Ltd.). In a nitrogen atmosphere, the spray nozzle size is about 5 μm, the pressure during spray-drying is about 0.4 MPa, and the atmosphere temperature during powder drying is about 200 °C.
[0209] The composition prepared under the above spray-drying conditions is sprayed to remove isopropyl alcohol therefrom, thereby preparing porous silicon secondary particles.
[0210] The obtained porous silicon secondary particles are used as a composite anode active material.
[0211] Comparative Example 2: Silicon Composite Structure
[0212] The porous silicon secondary particles prepared in Comparative Example 1 were charged into a reactor. While supplying CH4 to the reactor at about 350 sccm under 1 atm, the internal temperature of the reactor was raised to 1,000 °C at a heating rate of about 25 °C / min.
[0213] Subsequently, heat treatment was performed while maintaining the above temperature for 5 hours. Subsequently, the supply of CH4 was cut off and the internal temperature of the reactor was adjusted to room temperature (25 °C), and a silicon composite structure was obtained.
[0214] It was found that the obtained silicon composite structure included porous silicon secondary particles and highly crystalline first graphene sheets disposed on the porous silicon secondary particles. It was found that the porous silicon secondary particles included aggregates of two or more silicon composite primary particles. It was found that the silicon composite primary particles included: silicon; silicon monoxide (SiO x , 0 < x < 2), disposed on the silicon; and second graphene sheets, disposed on the silicon monoxide.
[0215] Relative to the total weight of 100 parts by weight of the silicon composite structure, the amount of the first graphene sheets and the second graphene sheets in the silicon composite structure was about 27 parts by weight. The silicon composite structure was porous.
[0216] The prepared silicon composite structure was used as a composite negative electrode active material.
[0217] Comparative Example 3: Silicon composite structure + first coating layer containing first amorphous carbon doped with external F
[0218] Using a planetary mixer, 45 parts by weight of the silicon composite structure prepared in Comparative Example 2, 5 parts by weight of polyvinylidene fluoride (PVDF), and 50 parts by weight of N-methylpyrrolidone were mixed to prepare a composition. Dry mixing of the composition was performed for 10 minutes.
[0219] The dry mixing was performed at 12,000 rpm, and the mixing temperature was controlled to about 50 °C. The mixed product was heat-treated at about 200 °C for 3 hours in an argon atmosphere.
[0220] A composite negative electrode active material having a first carbonaceous coating containing F-doped first amorphous carbon on the silicon composite structure was prepared.
[0221] Comparative Example 4: Silicon composite structure + external first amorphous carbon coating + infiltrated second amorphous carbon
[0222] Using a planetary mixer, 70 parts by weight of the silicon-containing composite structure prepared in Comparative Example 2, 20 parts by weight of coal tar pitch, and 10 parts by weight of N-methylpyrrolidone were added, and a mixing operation was performed.
[0223] Through the mixing operation, coal tar pitch penetrates into the gaps between the porous silicon secondary particles included in the silicon composite structure. The mixing operation for infiltrating the coal tar pitch is performed for a total of 4 cycles, wherein each cycle involves stirring-degassing-stirring in sequence and takes a total of 15 minutes, with each step performed for 5 minutes. In the stirring step, the rotational speed is 1,000 rpm and the self-rotating speed is 1,000 rpm, and in the degassing step, the rotational speed is 2,000 rpm and the self-rotating speed is 64 rpm, wherein 40 parts by weight of the above-mentioned coal tar pitch is divided into 4 parts, and each part is added to each cycle. The mixing temperature is controlled to about 70°C. The mixed product is heat treated at about 1,000°C for 4 hours under a nitrogen atmosphere.
[0224] As a result, a composite negative electrode active material having the first carbon-based coating layer including the first amorphous carbon on the silicon composite structure and including the second amorphous carbon disposed inside the silicon composite structure is prepared.
[0225] The second amorphous carbon is disposed in pores of the porous silicon secondary particles included in the silicon composite structure. The weight ratio of the first amorphous carbon to the second amorphous carbon is 1:2.
[0226] Comparative Example 5: Silicon composite structure + external first coating layer containing first amorphous carbon
[0227] Using a planetary mixer, 60 parts by weight of the silicon-containing composite structure prepared in Comparative Example 2, 60 parts by weight of coal tar pitch, and 20 parts by weight of N-methylpyrrolidone were mixed to prepare a composition. Dry mixing of the composition was performed for 10 minutes.
[0228] The dry mixing was performed at 12,000 rpm, and the mixing temperature was controlled to be about 50° C. The mixed product was heat-treated at about 1,000° C. for 3 hours under an argon atmosphere.
[0229] A composite negative electrode active material having a first carbon-based coating layer including first amorphous carbon on a silicon composite structure is prepared.
[0230] Example 1: Silicon composite structure + first carbon-based coating including first amorphous carbon doped with external F + infiltrated F doping The second amorphous carbon, doped with F content of 0.5wt%
[0231] Polyvinylidene fluoride (PVDF) was added to N-methylpyrrolidone and ultrasonicated for 30 minutes to prepare a 15 wt % PVDF solution.
[0232] In a Thinky mixer, 63 parts by weight of the silicon-containing composite structure prepared in Comparative Example 2, 3 parts by weight of PVDF, and 34 parts by weight of N-methylpyrrolidone were added and a mixing operation was performed.
[0233] Through the mixing operation, PVDF penetrates into the gaps between the porous silicon secondary particles included in the silicon composite structure. The mixing operation for infiltrating PVDF is performed for a total of 4 cycles, wherein each cycle takes a total of 15 minutes and involves stirring-degassing-stirring in sequence, and each step is performed for 5 minutes. In the stirring step, the rotational speed is 1,000 rpm and the self-rotating speed is 1,000 rpm, and in the degassing step, the rotational speed is 2,000 rpm and the self-rotating speed is 64 rpm, wherein the 10 wt% PVDF solution is divided into 3 parts, and each part is added to each cycle so that the total amount of PVDF added is equal to the amount of the above 3 parts by weight. The mixing temperature is controlled to about 70°C. The mixed product is heat treated at about 200°C for 3 hours under a nitrogen atmosphere.
[0234] As a result, a composite negative active material having a first carbon-based coating layer including F-doped first amorphous carbon on a silicon composite structure and including F-doped second amorphous carbon disposed inside the silicon composite structure was prepared.
[0235] The F-doped second amorphous carbon is disposed in pores of the porous silicon secondary particles included in the silicon composite structure. The weight ratio of the F-doped first amorphous carbon to the F-doped second amorphous carbon is 1:2.
[0236] In the prepared composite negative electrode active material, the weight ratio of carbon in the graphene sheet to carbon in the carbon-based coating is 7: 3. The graphene sheet here includes both the first graphene sheet and the second graphene sheet.
[0237] In the prepared composite negative electrode active material, the weight ratio of carbon in the graphene sheet to amorphous carbon is 7: 9. The amorphous carbon here includes both the first amorphous carbon and the second amorphous carbon.
[0238] Based on transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS) analysis of a cross section of the composite negative electrode active material, the content of fluorine doped in the second amorphous carbon was 0.5 wt %.
[0239] The fluorine content doped in the first amorphous carbon is the same as the fluorine content doped in the second amorphous carbon.
[0240] Example 2: Silicon composite structure + first carbon-based coating including first amorphous carbon with external F doping + infiltrated F doping The second amorphous carbon, doped with F content of 1wt%
[0241] A composite negative active material was prepared according to the same process as in Example 1, except that the PVDF content was changed so that the fluorine content doped into the second amorphous carbon became 1 wt %.
[0242] The fluorine content doped in the first amorphous carbon is the same as the fluorine content doped in the second amorphous carbon.
[0243] Example 3: Silicon composite structure + first carbon-based coating including first amorphous carbon doped with external F + infiltrated F doping The second amorphous carbon, doped with F content of 1.8wt%
[0244] A composite negative active material was prepared according to the same process as in Example 1, except that the PVDF content was changed so that the fluorine content doped into the second amorphous carbon became 1.8 wt %.
[0245] The fluorine content doped in the first amorphous carbon is the same as the fluorine content doped in the second amorphous carbon.
[0246] Example 4: Silicon composite structure + first carbon-based coating including first amorphous carbon with external F doping + infiltrated F doping The second amorphous carbon, doped with F content of 3.2wt%
[0247] A composite negative active material was prepared according to the same process as in Example 1, except that the PVDF content was changed so that the fluorine content doped into the second amorphous carbon became 3.2 wt %.
[0248] The fluorine content doped in the first amorphous carbon is the same as the fluorine content doped in the second amorphous carbon.
[0249] Example 5: Silicon composite structure + external F-doped first amorphous carbon coating + infiltrated F-doped second amorphous carbon + Carbon-based coating, doped with 1wt% F
[0250] Polyvinylidene fluoride (PVDF) was added to N-methylpyrrolidone and ultrasonicated for 30 minutes to prepare a 15 wt % PVDF solution.
[0251] 45 parts by weight of the silicon-containing composite structure prepared in Comparative Example 2, 5 parts by weight of polyvinylidene fluoride (PVDF), and 50 parts by weight of N-methylpyrrolidone were added to a Thinky mixer, and a mixing operation was performed.
[0252] Through the mixing operation, PVDF penetrates into the gaps between the porous silicon secondary particles included in the silicon composite structure. The mixing operation for infiltrating PVDF is performed for a total of 4 cycles, wherein each cycle takes a total of 15 minutes and involves stirring-degassing-stirring in sequence, and each step is performed for 5 minutes. The stirring rate in the stirring step is 1,000 rpm, and the rotation speed in the degassing step is 2,000 rpm, wherein the 10wt% PVDF solution is divided into 3 parts, and each part is added to each cycle so that the total amount of PVDF added is equal to the amount of the above 5 parts by weight. The mixing temperature is controlled to about 70°C to prepare a first mixed product.
[0253] 60 parts by weight of the thus prepared mixed product and 3 parts by weight of coal tar pitch were dry-mixed using a Thinky mixer. The dry mixing was performed at 2,000 rpm for 5 minutes, and the mixing temperature was controlled to about 70° C. to prepare a second mixed product.
[0254] The obtained second mixed product was introduced into a Nobilta mixer (Hosokawa Micoron, Japan), and ground at 7,000 rpm for 5 minutes while controlling the grinding temperature to about 50°C.
[0255] The ground product was heat-treated at about 150° C. for 3 hours under a nitrogen atmosphere, and then, after the temperature was increased to 1,000° C. at a rate of about 4° C. / min, heat-treated at the same temperature for 3 hours.
[0256] A composite negative electrode active material is prepared, in which a first carbon-based coating comprising a first amorphous carbon doped with F is arranged on a silicon composite structure, a second amorphous carbon doped with F is arranged inside the silicon composite structure, and a second carbon-based coating comprising a third amorphous carbon not doped with F is arranged on the first carbon-based coating.
[0257] Comparative Example 6: Silicon composite structure + external F-doped first amorphous carbon coating + infiltrated F-doped second amorphous Carbon, F is removed by high temperature heat treatment
[0258] A composite negative active material was prepared by the same process as in Example 1, except that the heat treatment temperature of the mixed product was changed from 200°C to 800°C.
[0259] Based on TEM and EDS analysis of the cross section of the composite negative electrode active material, fluorine doped in the second amorphous carbon was not detected. In addition, fluorine was not detected in the first amorphous carbon.
[0260] (Manufacturing of negative electrode and lithium full battery)
[0261] Example 6
[0262] (Manufacturing of negative electrode)
[0263] The slurry was prepared by mixing the composite negative electrode active material prepared in Example 1, graphite, CMC / SBR binder (1:1 weight ratio mixture) and deionized water. The mixing ratio of the mixture of the composite negative electrode active material and graphite to the solid content of the CMC / SBR binder was 97.5:2.5 by weight. In the mixture of the composite negative electrode active material and graphite prepared in Example 1, the weight ratio of the composite negative electrode active material to the graphite was 5:95.
[0264] On a copper foil current collector, the slurry was bar coated to a thickness of 50 μm, dried at room temperature, and vacuum dried again at 120 °C under vacuum, and then rolled to fabricate the negative electrode.
[0265] (Manufacturing of positive electrode)
[0266] Will contain LiNi in a weight ratio of 96:2:2 0.91 Co 0.05 Al0.04 A mixture of an O2 (hereinafter, referred to as NCA91) composite positive active material, a carbon conductive agent (Denka Black), and polyvinylidene fluoride (PVdF) was mixed with N-methylpyrrolidone (NMP) in an agate mortar to prepare a slurry.
[0267] The slurry was bar-coated to a thickness of 40 μm on an aluminum current collector, dried at room temperature, and dried again under vacuum at 120 °C, and then rolled to fabricate the positive electrode.
[0268] (Manufacture of coin cell batteries)
[0269] A coin cell was manufactured using the positive and negative electrodes manufactured above and a polypropylene separator (Celgard 3510), and using a solution containing 1.15M LiPF6 and 1.5wt% vinylene carbonate (VC) dissolved in EC (ethylene carbonate) + EMC (ethyl methyl carbonate) + DMC (dimethyl carbonate) (2:4:4 volume ratio) as an electrolyte.
[0270] Example 7 to Example 10
[0271] A coin cell was manufactured according to the same process as that of Example 6, except that the composite negative electrode active materials prepared in Examples 2 to 5 were used instead of the composite negative electrode active material prepared in Example 1, respectively.
[0272] Comparative Examples 7 to 12
[0273] A coin cell was manufactured according to the same process as that of Example 6, except that the composite negative electrode active materials prepared in Comparative Examples 1 to 6 were used instead of the composite negative electrode active material prepared in Example 1, respectively.
[0274] (Manufacturing of negative electrode and lithium half-cell)
[0275] Example 11
[0276] (Manufacturing of negative electrode)
[0277] The slurry was prepared by mixing the composite negative electrode active material prepared in Example 1, graphite, CMC / SBR binder (1:1 weight ratio mixture) and deionized water. The mixing ratio of the mixture of the composite negative electrode active material and graphite to the solid content of the CMC / SBR binder was 97.5:2.5 by weight. In the mixture of the composite negative electrode active material and graphite prepared in Example 1, the weight ratio of the composite negative electrode active material to the graphite was 5:95.
[0278] On a copper foil current collector, the slurry was bar coated to a thickness of 50 μm, dried at room temperature, vacuum dried again under vacuum conditions at 120 °C, and then rolled to fabricate the negative electrode.
[0279] (Manufacture of coin cell batteries)
[0280] A coin cell was fabricated using the fabricated negative electrode as a working electrode, a lithium metal electrode as a counter electrode, a polypropylene separator (Celgard 3510), and a solution comprising 1.15 M LiPF6 and 1.5 wt % vinylene carbonate (VC) dissolved in EC (ethylene carbonate) + EMC (ethyl methyl carbonate) + DMC (dimethyl carbonate) (2:4:4 volume ratio) as an electrolyte.
[0281] Comparative Example 13
[0282] A coin cell was manufactured according to the same process as that of Example 11, except that the composite negative electrode active material prepared in Comparative Example 2 was used instead of the composite negative electrode active material prepared in Example 1.
[0283] Evaluation Example 1: SEM Analysis
[0284] The SEM images of the surfaces of the composite negative electrode active materials prepared in Comparative Example 2, Example 1 and Example 5, as well as their specific surface areas ("BET" in the figure) and average particle sizes are shown in Figure 2a to Figure 2f and Table 1 below.
[0285] The specific surface area was measured by nitrogen porosimetry and the particle size was measured using a laser scattering particle size distribution analyzer.
[0286] Figure 2a and Figure 2b is a scanning electron microscope image of the composite negative electrode active material prepared in Comparative Example 2. Figure 2a As shown in , it was found that the composite negative electrode active material prepared in Comparative Example 2 had a non-spherical particle shape.
[0287] like Figure 2b As shown in , the composite negative active material of Comparative Example 2 shows increased surface irregularities due to including a plurality of carbon sheets disposed on the surface of the composite negative active material.
[0288] Figure 2c and Figure 2d is a scanning electron microscope image of the composite negative electrode active material prepared in Example 1. Figure 2c As shown in , it was found that the composite negative electrode active material prepared in Example 1 had a non-spherical particle shape.
[0289] like Figure 2dAs shown in , the composite negative active material of Example 1 shows reduced surface irregularities due to including the first carbon-based coating layer disposed on the surface of the composite negative active material.
[0290] Figure 2e and Figure 2f is a scanning electron microscope image of the composite negative electrode active material prepared in Example 5. Figure 2e As shown in , it was found that the composite negative electrode active material prepared in Example 5 had a spherical particle shape.
[0291] like Figure 2f As shown in , the composite negative active material of Example 5 further reduces surface irregularities because it further includes a second carbon-based coating layer disposed on the first carbon-based coating layer.
[0292] [Table 1]
[0293]
[0294] like Figure 2a to Figure 2f As shown in Table 1, a gradual decrease in specific surface area was observed in the composite negative active materials prepared in Comparative Example 2, Example 2, and Example 5.
[0295] The composite negative electrode active materials prepared in Comparative Example 2 and Example 2 had non-spherical particle shapes, but the composite negative electrode active material prepared in Example 5 had a spherical particle shape.
[0296] Although not shown in the accompanying drawings, the SEM image of the cross section of the composite negative electrode active material prepared in Comparative Example 5 confirms the presence of multiple pores on the surface of the cross section. Therefore, it is confirmed that the silicon-containing composite structure inside the composite negative electrode active material prepared in Comparative Example 5 is porous. At the same time, although not shown in the accompanying drawings, in the SEM images of the cross sections of the composite negative electrode active materials prepared in Comparative Example 4 and Examples 1 to 5, there are no observable multiple pores on the surface of the cross section. Therefore, it is confirmed that the silicon-containing composite structure inside the composite negative electrode active materials prepared in Comparative Example 4 and Examples 1 to 5 is non-porous.
[0297] Evaluation Example 2: HAADF-TEM and STEM-EDS Analysis
[0298] The cross section of the composite negative electrode active material prepared in Example 2 was subjected to HAADF-STEM (high angle annular dark field scanning transmission electron microscope) and STEM-EDS (energy dispersive X-ray spectrometer) element mapping analysis, and the results are shown in Figures 3a to 3f middle.
[0299] like Figure 3a As shown in , the silicon-containing composite structure includes porous silicon secondary particles having a structure including an aggregate of a plurality of silicon composite primary particles.
[0300] like Figure 3b As shown in , the silicon primary particles were found to have a needle-like shape and / or a eutectic shape.
[0301] like Figure 3c As shown in , the second amorphous carbon was found to exist in the spaces between the primary silicon particles.
[0302] like Figure 3d As shown in , the doped fluorine was found to be present in the second amorphous carbon. In addition, the doped fluorine atoms were found to be disposed adjacent to the silicon primary particles.
[0303] like Figure 3e and Figure 3f As shown in , the amounts of elements present in the region A where the second amorphous carbon was mainly provided and the region B where the primary silicon particles were mainly provided were measured, and the results thereof are shown in Table 2 below.
[0304] [Table 2]
[0305] Fluorine content [wt%] Region A 1.5 Region B 0.2
[0306] like Figure 3f As shown in Table 2, the content of fluorine (F) doped into the region A where the second amorphous carbon is mainly provided is 1.5 wt % with respect to the total amount of elements in the region A.
[0307] Meanwhile, the fluorine (F) content doped in the region B where the silicon primary particles are mainly disposed is negligible.
[0308] Therefore, it was confirmed that fluorine (F) was doped into the second amorphous carbon filled inside the silicon-containing composite structure in the composite negative electrode active material prepared in Example 2.
[0309] Although not shown in the drawings, it is confirmed that fluorine (F) is also doped into the first carbon-based coating layer coated on the silicon-containing composite structure. That is, the first amorphous carbon is also doped with fluorine.
[0310] Evaluation Example 3: Evaluation of Cycle Characteristics at Room Temperature (25°C) (I)
[0311] The lithium batteries prepared in Examples 6 to 9 and Comparative Examples 7 and 8 were each charged at a constant current of 0.1C rate at 25°C until the voltage reached 4.5V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during discharge, each battery was discharged at a constant current of 0.1C rate until the battery voltage reached 2.75V (vs. Li) (formation cycle).
[0312] The lithium batteries after the formation cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during the discharge period, each battery was discharged at a constant current of 0.5C rate until the battery voltage reached 2.75V (vs.Li) (1st cycle). The above cycle was repeated under the same conditions until the 165th cycle (repeated 165 times).
[0313] In all charge-discharge cycles, a 10-minute rest period was provided after each charge / discharge cycle. A portion of the room temperature cycle test results are shown in Table 3 below. The capacity retention ratio is defined by the following equation 1. The discharge capacity is the discharge capacity at the 165th cycle.
[0314] <Equation 1>
[0315] Capacity retention rate [%] = [discharge capacity at the 165th cycle / discharge capacity at the 1st cycle] × 100
[0316] [Table 3]
[0317]
[0318] As shown in Table 3, the lithium batteries of Examples 6 to 9 exhibited improved discharge capacity and lifespan characteristics compared to the lithium batteries of Comparative Examples 7 and 8.
[0319] It is believed that these improvements in discharge capacity and life characteristics are attributed to the fact that the fluorine-doped second amorphous carbon is arranged inside the silicon-containing composite structure and the fluorine-doped first amorphous carbon is arranged on the silicon-containing composite structure so that a modified solid electrolyte interface (SEI) is formed on the surface and / or inside the composite negative electrode active material, thereby suppressing the internal resistance of the lithium battery.
[0320] For example, including a lithium conductive inorganic compound derived from fluorine (F) (e.g., LiF and Li2O) inside or on the surface of the composite negative electrode active material during the cycle of the lithium battery can form a stable SEI with improved mechanical strength and lithium ion conductivity. It is therefore believed that effectively suppressing the side reactions caused by the electrolyte inside and / or on the surface of the composite negative electrode active material contributes to the above-mentioned improvements. In addition, it is believed that these improvements are attributed to the fact that the flaky carbon directly grown and arranged on the silicon inside the composite negative electrode active material effectively adapts to the volume change of silicon.
[0321] Evaluation Example 4: Evaluation of Cycle Characteristics at Room Temperature (25°C) (II)
[0322] The lithium batteries prepared in Example 7 and Comparative Examples 8 and 9 were each charged at a constant current of 0.1C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during discharge, each battery was discharged at a constant current of 0.1C rate until the battery voltage reached 2.75V (vs.Li) (formation cycle).
[0323] The lithium batteries after the formation cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during the discharge period, each battery was discharged at a constant current of 0.2C rate until the battery voltage reached 2.75V (vs.Li) (1st cycle). The above cycle was repeated under the same conditions until the 165th cycle (repeated 165 times).
[0324] In all charge-discharge cycles, a 10-minute rest period was provided after each charge / discharge cycle. A portion of the room temperature charge-discharge test results are shown in Table 4 below. The capacity retention rate is defined by the following equation 1. The discharge capacity is the discharge capacity at the 165th cycle.
[0325] <Equation 1>
[0326] Capacity retention rate [%] = [discharge capacity at the 165th cycle / discharge capacity at the 1st cycle] × 100
[0327] [Table 4]
[0328]
[0329] As shown in Table 4, the lithium battery of Example 7 exhibited improved discharge capacity and lifespan characteristics compared to the lithium batteries of Comparative Examples 8 and 9.
[0330] These improvements in discharge capacity and lifespan characteristics are considered to be attributed to the fact that the F-doped second amorphous carbon penetrates into the silicon-containing composite structure so that the silicon-containing composite structure is more effectively protected during cycling of the lithium battery.
[0331] Evaluation Example 5: Evaluation of Cycle Characteristics (III) at Room Temperature (25°C)
[0332] The lithium batteries prepared in Example 7 and Comparative Example 10 were each charged at a constant current of 0.1C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during discharge, each battery was discharged at a constant current of 0.1C rate until the battery voltage reached 2.75V (vs.Li) (formation cycle).
[0333] The lithium batteries after the formation cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during the discharge period, each battery was discharged at a constant current of 0.2C rate until the battery voltage reached 2.75V (vs.Li) (1st cycle). The above cycle was repeated under the same conditions until the 165th cycle (repeated 165 times).
[0334] In the above-mentioned entire charge-discharge cycle, a rest time of 10 minutes was provided after each charge / discharge cycle. A part of the room temperature charge-discharge test results is shown in Table 5 below. The capacity retention rate is defined by the following equation 1. The discharge capacity is the discharge capacity of the 165th cycle.
[0335] <Equation 1>
[0336] Capacity retention rate [%] = [discharge capacity at the 165th cycle / discharge capacity at the 1st cycle] × 100
[0337] [Table 5]
[0338]
[0339] As shown in Table 5, the lithium battery of Example 7 exhibited improved discharge capacity and lifespan characteristics compared to the lithium battery of Comparative Example 10.
[0340] These improvements in discharge capacity and life characteristics are believed to be attributed to the fact that fluorine doping of the second amorphous carbon disposed inside the silicon-containing composite structure allows more effective suppression of side reactions inside the silicon-containing composite structure during cycling of the lithium battery.
[0341] Evaluation Example 6: Evaluation of Cycle Characteristics (IV) at Room Temperature (25°C)
[0342] The lithium batteries prepared in Example 10 and Comparative Examples 8 and 11 were each charged at a constant current of 0.1C rate at 25°C until the voltage reached 4.5 V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5 V. Subsequently, during discharge, each battery was discharged at a constant current of 0.1C rate until the battery voltage reached 2.75 V (vs. Li) (formation cycle).
[0343] The lithium batteries after the formation cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during the discharge period, each battery was discharged at a constant current of 0.2C rate until the battery voltage reached 2.75V (vs.Li) (1st cycle). The above cycle was repeated under the same conditions until the 165th cycle (repeated 165 times).
[0344] In all charge-discharge cycles, a 10-minute rest period was provided after each charge / discharge cycle. A portion of the room temperature charge-discharge test results are shown in Table 6 below. The capacity retention rate is defined by the following equation 1. The discharge capacity is the discharge capacity at the 165th cycle.
[0345] <Equation 1>
[0346] Capacity retention rate [%] = [discharge capacity at the 165th cycle / discharge capacity at the 1st cycle] × 100
[0347] [Table 6]
[0348]
[0349] As shown in Table 6, the lithium battery of Example 10 exhibited improved discharge capacity and lifespan characteristics compared to the lithium batteries of Comparative Examples 8 and 11.
[0350] These improvements in discharge capacity and life characteristics are believed to be attributed to the fact that fluorine-doping of the fluorine-doped second amorphous carbon inside the silicon-containing composite structure allows more effective suppression of side reactions inside the silicon-containing composite structure during cycling of the lithium battery.
[0351] In addition to the first carbon coating, the second carbon coating is further included on the silicon-containing composite structure to further improve the structural stability of the composite negative electrode active material.
[0352] Evaluation Example 7: Evaluation of Interface Resistance
[0353] Before and after cycling, the pellet impedance of the lithium batteries prepared in Example 12 and Comparative Example 13 was measured by a double probe method using an impedance analyzer (Solartron 1400A / 1455A impedance analyzer). The frequency range was 0.1 Hz to 1 MHz, and the amplitude voltage was 10 mV. The measurements were performed in an ambient atmosphere at 25°C. The Nyquist plots obtained from the impedance measurements are shown in Table 1. Figure 4a and Figure 4b Shown in.
[0354] Figure 4a Impedance measurement results of the lithium batteries of Example 12 and Comparative Example 13 before cycling are shown.
[0355] Figure 4b Impedance measurement results of the lithium batteries of Example 12 and Comparative Example 13 after cycling are shown.
[0356] The battery was cycled under the following conditions.
[0357] The lithium batteries prepared in Example 12 and Comparative Example 13 were each charged at a constant current of 0.1C rate at 25°C until the voltage reached 4.5 V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5 V. Subsequently, during discharge, each battery was discharged at a constant current of 0.1C rate until the battery voltage reached 2.75 V (vs. Li) (formation cycle).
[0358] The lithium batteries after the formation cycle were each charged at a constant current of 0.5C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during the discharge period, each battery was discharged at a constant current of 0.5C rate until the battery voltage reached 2.75V (vs.Li) (1st cycle). The above cycle was repeated under the same conditions until the 50th cycle (repeated 50 times).
[0359] like Figure 4a As shown in , the interface resistances of the lithium batteries of Example 12 and Comparative Example 13 were similar before cycling.
[0360] At the same time, if Figure 4b As shown in FIG. 1 , after the cycle, the resistance component R caused by charge transfer of the lithium battery of Comparative Example 13 is lower than that of the lithium battery of Example 12. SEI showed a significant increase.
[0361] It is believed that this difference may be attributed to the fact that in the composite negative electrode active material included in the lithium battery of Example 12, the F-doped second amorphous carbon is arranged inside the silicon-containing composite structure, and since the solid electrolyte interface derived from the second amorphous carbon contains components such as LiF and / or Li2O, the ionic conductivity, mechanical properties and stability of the solid electrolyte interface are increased, which reduces the internal resistance of the lithium battery.
[0362] Evaluation Example 8: Evaluation of room temperature high rate discharge capability
[0363] The lithium batteries prepared in Example 12 and Comparative Example 13 were each charged at a constant current of 0.1C rate at 25°C until the voltage reached 4.5 V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5 V. Subsequently, during discharge, each battery was discharged at a constant current of 0.2C rate until the battery voltage reached 2.75 V (vs. Li) (formation cycle).
[0364] The lithium batteries after the formation cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5V (vs.Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5V. Subsequently, during the discharge period, each battery was discharged at a constant current of 0.2C rate until the battery voltage reached 2.75V (vs.Li) (1st cycle).
[0365] The lithium batteries after the first cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5 V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5 V. Subsequently, during discharge, each battery was discharged at a constant current of 0.5C rate until the battery voltage reached 2.8 V (vs. Li) (2nd cycle).
[0366] The lithium batteries after the second cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5 V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5 V. Subsequently, during discharge, each battery was discharged at a constant current of 1.0C rate until the battery voltage reached 2.8 V (vs. Li) (3rd cycle).
[0367] The lithium batteries after the third cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5 V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5 V. Subsequently, during discharge, each battery was discharged at a constant current of 3.0C rate until the battery voltage reached 2.8 V (vs. Li) (4th cycle).
[0368] The lithium batteries after the 4th cycle were each charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.5 V (vs. Li), and then charged at a current cutoff of 0.02C rate in constant voltage mode while maintaining 4.5 V. Subsequently, during discharge, each battery was discharged at a constant current of 4.0C rate until the battery voltage reached 2.8 V (vs. Li) (5th cycle).
[0369] In the above-mentioned entire charge-discharge cycle, a rest time of 10 minutes was provided after each charge / discharge cycle. The results of the room temperature high rate discharge capability test are shown in Table 7 below. The high rate capability is defined by Equation 5 below.
[0370] <Equation 5>
[0371] High rate capacity [%] = [discharge capacity at the nth cycle / discharge capacity at the first cycle] × 100
[0372] [Table 7]
[0373]
[0374] As shown in Table 7, the coated lithium battery of Example 12 exhibited improved high rate capability compared to the lithium battery of Comparative Example 13.
[0375] The improvement in the high rate capability of the lithium battery of Example 11 is considered to be attributable to the fact that the lithium battery of Example 12 has reduced internal resistance by including the composite negative active material including the F-doped second amorphous carbon prepared in Example 1.
[0376] Industrial Applicability
[0377] According to one aspect, since the composite negative active material includes the second amorphous carbon doped with a foreign element, the lithium battery may have an increased discharge capacity and improved cycle characteristics.
Claims
1. A composite negative electrode active material, comprising: Silicon-containing composite structure; a first carbon-based coating, comprising a first amorphous carbon and disposed on the silicon-containing composite structure; as well as a second amorphous carbon disposed in the silicon-containing composite structure, The silicon-containing composite structure includes: porous silicon secondary particles; and a first carbon sheet disposed on the porous silicon secondary particles. The porous silicon secondary particles each include an aggregate comprising a plurality of silicon composite primary particles, Wherein, the silicon composite primary particles include silicon, silicon dioxide SiO disposed on the silicon x and a second carbon sheet disposed on the silicon oxide, wherein 0 <x<2, The second amorphous carbon is disposed in the pores of the porous silicon secondary particles, and The second amorphous carbon includes a foreign element belonging to at least one selected from Group 15 and Group 17 of the periodic table.
2. The composite negative electrode active material according to claim 1, in, The foreign element is at least one selected from fluorine, nitrogen and phosphorus.
3. The composite negative electrode active material according to claim 1, in, On an energy dispersive X-ray spectrometer spectrum of the silicon-containing composite structure in which the second amorphous carbon is disposed, a content of the foreign element relative to a total amount of elements is 0.1 wt % to 10 wt %.
4. The composite negative electrode active material according to claim 1, in, The second amorphous carbon is disposed on the second carbon sheet, The second amorphous carbon is separated from the silicon by the second carbon sheet, and The foreign element in the second amorphous carbon is disposed adjacent to the silicon.
5. The composite negative electrode active material according to claim 1, in, The first amorphous carbon includes a foreign element belonging to at least one selected from Group 15 and Group 17 of the periodic table.
6. The composite negative electrode active material according to claim 5, in, On an energy dispersive X-ray spectrometer spectrum of the first carbon-based coating layer including the first amorphous carbon, the content of the foreign element relative to the total amount of elements is 0.1 wt % to 10 wt %.
7. The composite negative electrode active material according to claim 1, in, The first amorphous carbon is disposed on the first carbon sheet, and The first amorphous carbon is separated from the silicon by the first carbon sheet.
8. The composite negative electrode active material according to claim 1, in, The composite negative electrode active material has a porosity of 30% or less, or is non-porous.
9. The composite negative electrode active material according to claim 1, in, The first carbon-based coating is non-porous and has a thickness of 1 nm to 5,000 nm.
10. The composite negative electrode active material according to claim 1, in, The first carbon sheet and the second carbon sheet each independently include graphene, graphite, carbon fiber, graphite carbon, graphene oxide or a mixture thereof, and The first amorphous carbon and the second amorphous carbon each independently include polymer carbide, pitch carbon, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, carbon fiber, or a mixture thereof.
11. The composite negative electrode active material according to claim 1, in, A mixing ratio of a total weight of the first carbon sheet and the second carbon sheet to a total weight of the first amorphous carbon and the second amorphous carbon is 30:1 to 1:
3.
12. The composite negative electrode active material according to claim 1, in, The composite negative electrode active material has a non-spherical particle form, and the composite negative electrode active material has a particle size of 1 m 2 / g to 20m 2 / g specific surface area, The silicon has a form selected from spheres, needles, rods, particles, nanowires, nanotubes, nanorods, wafers, nanobelts, or mixtures thereof, and The silicon has an average size of 10 nm to 1,000 nm.
13. The composite negative electrode active material according to claim 1, further comprising a second carbon coating disposed on the first carbon coating, in, The second carbon-based coating includes a third amorphous carbon, and The third amorphous carbon does not contain a foreign element belonging to at least one selected from Group 15 and Group 17 of the periodic table.
14. The composite negative electrode active material according to claim 13, in, The third amorphous carbon includes pitch carbon, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, carbon fiber or a mixture thereof.
15. The composite negative electrode active material according to claim 13, in, The composite negative electrode active material has a spherical particle form, and the composite negative electrode active material has a 1m 2 / g to 10m 2 / g specific surface area.
16. The composite negative electrode active material according to claim 1, in, The composite negative electrode active material has an average particle size D50 of 1 μm to 10 μm, a particle size D10 of 0.1 μm to 7 μm, and a particle size D90 of 10 μm to 30 μm.
17. The composite negative electrode active material according to claim 1, further comprising a lithium compound disposed in the silicon-containing composite structure, in, The lithium compound includes at least one selected from LiF and Li2O. 18 . A negative electrode, comprising the composite negative electrode active material according to claim 1 .
19. A lithium battery, comprising: positive electrode; The negative electrode according to claim 18; as well as An electrolyte is provided at the positive electrode and the negative electrode.
20. The lithium battery according to claim 19, in, The electrolyte includes a liquid electrolyte, a solid electrolyte, a gel electrolyte or a combination thereof, the solid electrolyte includes an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer solid electrolyte or a combination thereof, and the gel electrolyte includes a polymer gel electrolyte.
21. The lithium battery according to claim 19, in, The positive electrode includes a positive electrode current collector, and the negative electrode includes a negative electrode current collector, Among them, at least one of the positive electrode collector and the negative electrode collector includes a base film and a metal layer on one side or both sides of the base film, the base film includes a polymer, the polymer includes polyethylene terephthalate, polyethylene, polypropylene, polybutylene terephthalate, polyimide or a combination thereof, and the metal layer includes indium, copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, lithium or an alloy thereof.
22. A method for preparing a composite negative electrode active material, the method comprising the following steps: providing porous silicon secondary particles; preparing a silicon-containing composite structure by supplying a carbon source gas to the porous silicon secondary particles and performing a heat treatment on the porous silicon secondary particles; preparing a first composition including the silicon-containing composite structure, an amorphous carbon precursor including a foreign element belonging to Group 15 or Group 17 of the periodic table, and an additive; and The composite negative electrode active material is prepared by heat-treating the first composition at a temperature of 350° C. or lower, Wherein, the composite negative electrode active material comprises: Silicon-containing composite structure; a first carbon-based coating, comprising a first amorphous carbon, and disposed on the silicon-containing composite structure; and a second amorphous carbon disposed in the silicon-containing composite structure, The silicon-containing composite structure includes: porous silicon secondary particles; and a first carbon sheet disposed on the porous silicon secondary particles. The porous silicon secondary particles each include an aggregate comprising a plurality of silicon composite primary particles, Wherein, the silicon composite primary particles include silicon, silicon dioxide SiO disposed on the silicon x and a second carbon sheet disposed on the silicon oxide, wherein 0 <x<2, The second amorphous carbon is disposed in the pores of the porous silicon secondary particles, and The second amorphous carbon includes a foreign element belonging to at least one selected from Group 15 and Group 17 of the periodic table.